Effect of sodium hexametaphosphate on the flotation separation of biotite and K-feldspar in the NaOL/DDA system - Xingyu Hu; Bo Mei; Lingfeng Shen; Wei Sun; Yanxiu Wang; Jinghua Huang; Li Wang (Minerals Engineering, 2026)

Comparative genomic epidemiology of food- and patient-derived diarrheagenic Escherichia coli from sentinel surveillance in Southeast China - Xiaomeng Huang; Li Gong; Fuming Liu; Jianhua Mei; Jinkai Li; Siyu Fu; Liyang Qiu; Deyong Zhang; Xiuying Chen (International Journal of Food Microbiology, 2026)

Effects of sampling strategy, geographical origin, and soil on stable isotopes and multi-elements for the traceability of Chinese PGI oranges - Jiahui Wu; Hao Deng; Guang Wu; Hanyi Mei; Karyne M. Rogers; Yurong Huang; Shengzhi Shao; Chunlin Li; Ping Wang; Jing Nie; Yuwei Yuan; Yongzhi Zhang (Food Control, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Berberine impedes the DNA damage repair to inhibit colorectal cancer by regulating the SOX17/TCF4/PIM3 axis - Fan Hu; Wei Wang; Mei Li; Qian Shi; Junjie Que; Pan Huang (Molecular Genetics and Genomics, 2026)

Integrative characterization of tissue-specific 3D genome organization and associated transcriptional regulation in pig liver and muscle - Weiwei Zhou; Yani Huang; Chenyu Li; Mei Ge; Mingfang Zhou; Huashui Ai; Zhiyan Zhang (Functional & Integrative Genomics, 2026)

MDA5 associates with MAVS and its splicing variant in the antiviral response of large yellow croaker Larimichthys crocea - Ying Li; Yi Fan Zhang; Xia Ming Chen; Qiang Ma; Jiao Nan Zhang; Xiao Mei Huang; Jing Xuan Li; Yu Xuan Zhu; Tuan Yu Guo; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

A Neoproterozoic arc-backarc system in the northern Yangtze Block: Implications for crustal growth and Rodinia reconstructions - Chao Chen; Hao Deng; Jin-Ling Yuan; Timothy Kusky; Qiang Chen; Zhen-Bing She; Ling-Yao Kong; Jiang Zhu; Hong-Mei Li; Jing-Meng Huang; Guo-Hu Wang; Cheng Yang; et al. (Earth-Science Reviews, 2026)

Valorizing lignocellulosic biomass-derived hydrothermal carbonization aqueous phase for heavy metal removal from contaminated soil: Molecular composition-mediated metal-specific complexation - Mei Huang; Yangchun Li; Yangziyun Zhang; Zhi Liao; Li Zhao; Dong Tian; Yan Liu; Yongjia Lei; Yu Zhao; Shuanglin Chen; Fei Shen (Bioresource Technology, 2026)

AIE-active photoresponsive Ir(III) complex as an oxidase mimic for ratiometric ascorbic acid detection - Qianghui Zheng; Ping Huang; Ying Peng; Mei-Jin Li; Fengfu Fu (Analytica Chimica Acta, 2026)

Cu2O@Fe Prussian blue-integrated smartphone-assisted sensing strategy for hydroquinone and bisphenol A determination - Jian-Mei Chen; Yong-Qi Ding; Yan-Hong Zhou; Zi-Xuan Bai; Xiao-Tong Yang; Xin Huang; Shuai Li; Feng-Zhan Sun (Food Chemistry, 2026)

Development and optimization of analytical methods for rapid detection of multiple mycotoxins in wheat products and dietary risk assessment - Kuan-Hsun Li; Mei-Jen Huang; Tomohisa Ogawa; Tseng-Yu Tsai; Hong-Da Hua; Deng-Jye Yang (Food Chemistry, 2026)

Development of TM hypoallergenic enzymatic products with the potential to induce immune tolerance in Lateolabrax japonicus - Meng-Si Li; Qing-Mei Liu; Fei Xia; Su-Jie Huang; Shun-Xian Lin; Li-Qiang Zhong; Hao-Tian Zhang; Gui-Xia Chen; Guang-Ming Liu (Food Bioscience, 2026)

Establishment of a novel brain cell line from grass carp (Ctenopharyngodon idella) with high transfection efficiency and CRISPR/Cas9-mediated genome editing capacity - Zi-Ling Qu; Tao Liu; Tang-Kai-Yuan Qin; Hua-Mei Yue; Ling Huang; Rui Ruan; Chang-Song Wu; Huan Ye; Chuang-Ju Li (Fish & Shellfish Immunology, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

A fish-skin-inspired wearable scale-ionogel composite for impact protection and motion sensing - Tianyu Xu; Zimu Li; Lin Mei; Hanshen Huang; Jie Tian; Zijian Mei; Shuting Liu; Xiaoming Liu; Xinglong Gong; Tianzhi Luo (Chemical Engineering Journal, 2026)

Spatial distribution and compositional profile of microplastics in oil and gas extraction solid wastes: An overlooked source of microplastics - Yongxu Jin; Jianqi Dai; Xiang Wang; Shan Zhong; Yingzhou Huang; Xudong Mei; Shijie Wang; Min Hao; Jinwei Fang; Yunmin Zeng; Dong Li (Chemical Engineering Journal, 2026)

Scalable cancer cell-derived liposome capable of homologous tumor-homing to encapsulate near-infrared light-responsive drug delivery nanocomposites for enhanced combination therapy - Fang-Yi Hsu; Wen-Jyun Wang; Li-Ting Yang; Yi-Zi Chen; Ting-Chi Lo; Jia-Sin Chen; Wei-Lun Huang; Yen-Liang Li; Hidenobu Takahashi; Wen-Chun Hung; Chi-Wen Luo; Shu-Yi Lin; et al. (Chemical Engineering Journal, 2026)

Tamarind shell extract alleviates oxidative stress-related developmental bone injury across complementary models via the Nrf2/GCLC/GCLM antioxidant axis - Gu Xiaoyuan; Mao Jianghao; Mei Aoyu; Ma Li; Ma Juan; Sun Pinghua; Huang Rongping; Li Weixi (PharmaNutrition, 2026)

Assessing the impacts of ecotourism on perceived ecosystem services and livelihoods: a case study in the Hani Terraces, China - Zhongde Huang; Degui Fu; Maroof Ali; Zhengchang Ma; Mei Li; Xiong Luo; Anjian He; Yang Bai (Journal of Outdoor Recreation and Tourism, 2026)

The distribution and characteristics of soil microplastics pollution: Evidences from different land use - Yandan Wang; Wuping Huang; Runran Mei; Changqun Duan; Guoqin Peng; Zhiming Yu; Shiyu Li (Journal of Hazardous Materials, 2026)

Intensive mariculture promotes molecular reorganization of dissolved organic matter in coastal waters - Kai Shen; Niangming Duan; Zhibing Jiang; Jiang Shen; Haibo Jiang; Hailong Huang; Lingfeng Zhou; Dongping Shi; Mei Li; Ying Kang; Yuanhao Wang; Xubiao Yu (Environmental Research, 2026)

Co-application of biochar and silicon fertilizer enhances rice nutrient allocation, soil fertility, and mitigates ARG dissemination in paddy soil - Mei Wang; Shuai Li; Hongwei Xu; Qiying Huang; Zhenyu Wang; Xudong Wang; Jiawei Ma (Environmental Research, 2026)

Quantifying human disturbance to landscape connectivity using the probability of connectivity disturbance index (PCDI): Evidence from 30 Chinese cities, 1990–2020 - Hao Li; Xinyan Huang; Ziyu Mei; Zhikai Zheng; Dongkai Zhang; Zhicheng Liu (Environmental Impact Assessment Review, 2026)

Extraction-driven structural modulation dictates the anti-diabetic potency of Notopterygium franchetii polysaccharides - Yabin Zhao; Shuang Huang; Yongxiang Luo; Huaiju Gong; Yukun Mei; Xin Tang; Renlin Zheng; Renjun Tian; De Zhou; Liangchun Li (Carbohydrate Polymers, 2026)

Overcoming the ''turn-off'' limitation via steric hindrance: A ''turn-on'' dual-readout nanozyme array based on spindle-shaped Prussian blue for highly selective discrimination of glutathione and food additives - Mei Li; Tianhui Huang; SuXuan Liao; Hailin Zhang; Jiakuan Wu; Qiuping Huang (Analytica Chimica Acta, 2026)

Insights Into Continuous Fertilization on the Profiles of Soil Bacterial Community, Antibiotic Resistance Genes, and Virulence Factors in a 10-year Oilseed Rape Field Experiment - Hongwei Xu; Shuai Li; Huangze Xu; Yi Ding; Qiying Huang; Jiawei Ma; Mei Wang (Journal of Soil Science and Plant Nutrition, 2026)

A new dipeptide from entomogenous fungus Metapochonia suchlasporia Y9 - Hong-Yan Yang; Jia-Qian Yang; Zhi-Pu Huang; Ke-Tao Zhang; Xin-Yi Chen; Jin-Li Zhao; Yan Wang; Qing Zhao; Xiao-Mei Zhang (Natural Product Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Structurally diverse clerodane diterpenoids with anti-inflammatory and anti-diabetic effects from Tinospora crispa (L.) Hook.f. & Thomson - Xianghong Chen; Tian Gao; Qiang Wang; Yiyang Yuan; Chenyang Yu; Jun Li; Xianju Huang; Hui Xiong; Zhinan Mei; Guangzhong Yang; Yu Chen (Phytochemistry, 2026)

Corrigendum to “Assessing the impacts of ecotourism on perceived ecosystem services and livelihoods: a case study in the Hani Terraces, China” [Journal of Outdoor Recreation and Tourism 55 (2026) 101077] - Zhongde Huang; Degui Fu; Maroof Ali; Zhengchang Ma; Mei Li; Xiong Luo; Anjian He; Yang Bai (Journal of Outdoor Recreation and Tourism, 2026)

Biochar increases plant biomass and reshapes biomass allocation through coordinated belowground and aboveground responses - Mei Yang; Jiahuan Guo; Juan Du; Lei Feng; Wenqiong Li; Mengke Huang; Hui Zhang; Huili Feng (Journal of Cleaner Production, 2026)

Inhibitory effects of fruit powders on heterocyclic amine formation in charcoal-grilled pork: A comparative study of application methods and development of a functional barbecue sauce spray - Mei-Ling Li; Yu-Shun Lin; Pei-Yu Wu; Ling-Hsuan Chang; Shang-Ming Huang; Kuo-Chiang Hsu (Food Research International, 2026)

From solvent-tailored carbon dots to a practical sensor array: fingerprint discrimination and quantification of azo dyes in beverages - Zhi-Min Zhi; Zong-Mei Huang; Cong-Ting Wu; Jing Li; Yanting Song; Lu-Shuang Li (Food Chemistry, 2026)

Chitosan-assisted cinnamaldehyde utilization and sodium carboxymethyl cellulose-enabled redispersion: A dual strategy for pathogen-specific grape preservation - Yidan Zhang; Lianghuan Huang; Mei Li; Juan Yang; Jisheng Yang; Ningjing Sun; Jialong Wen; Zhiyong Qin (Food Chemistry, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Biomass-assisted water electrolysis with liquid antimony anode for high efficiency hydrogen evolution - Xin Gu; Mei Zhou; Yidong Jiang; Yuting Li; Chaojun Liu; Jiongyuan Huang; Wenfei Mo; Xiaoyi Liu; Huihuang Fang; Wei Yan; Kongfa Chen; Yixiang Shi; et al. (Chemical Engineering Journal, 2026)

Impact of Eurasian zonal circulation index anomalies on vegetation activity across Eurasia - Liufeng Liao; Mei Huang; Ying Duan; Kun Zhang; Zhaosheng Wang; Li Dan (Theoretical and Applied Climatology, 2026)

Phosphate adsorption by activated dolomite and its impact on phosphorus availability in acidified soils - Chongqing Mei; Jiaxue Sun; Fanmin Zhu; Zhanbin Huang; Chuanfu Li (Journal of Soils and Sediments, 2026)

B-MARCO: a blockchain-driven multi-national auction and resource optimization framework for cross-border logistics and trade - Mei Sha; Shuang Li; Tao Zhang; Han Liu; Jianli Shen; Xiaohu Huang; Jiahua Hu (Frontiers in Marine Science, 2026)
Cross-border maritime logistics requires coordination among carriers, ports, customs authorities, and financial institutions, yet existing workflows are often constrained by fragmented regulatory data systems, inefficient dynamic capacity matching, and slow batch-based clearing. This paper proposes B-MARCO, a blockchain-driven multi-national auction and resource optimization framework for cross-border maritime logistics. B-MARCO integrates permissioned consortium coordination, rolling auction-based market clearing, a hybrid GA-GSA dispatching engine, and privacy-preserving access-control and compliance-verification components. The evaluation uses a semi-synthetic discrete-event simulation with a 7-day horizon, hourly decision intervals, 30 random seeds, and shared order streams across all configurations. Under a 5,000-orders/day workload, B-MARCO achieves a 91.80% transaction success rate and 21.53 h average end-to-end latency, compared with 60.09% and 36.66 h for the 24-hour batch-clearing baseline. Relative to a centralized rolling-matching baseline, it reduces average latency by 13.60%. The ablation results show that rolling auction clearing reduces latency, while smart-contract-based settlement-delay reduction is a major contributor to improved success and deadline performance. These findings support the value of combining rolling market clearing with spatial-temporal dispatch optimization in simulated cross-border maritime logistics, while the blockchain and cryptographic modules define the broader coordination, auditability, and data-governance architecture.

EasyAphid: a comprehensive method for aphid infestation quantification in wheat using EVC-YOLO-Seg model and RGB images - Haotian Deng; Hui Deng; Jiawei Chen; Xin Liu; Zijun Pei; Chenzhao Gao; Qi Sun; Xin Zhang; Shijie Zhai; Xueli Hu; Shuming Fan; Xiao Wang; et al. (Computers and Electronics in Agriculture, 2026)

Efficient capture of Cs+ ions by two supertetrahedral cluster-based microporous metal chalcogenides in neutral and alkaline environments - Ya-Dong Wu; Lu Yang; Zhi-Hua Chen; Hai-Yan Sun; Chuan Lv; Xiao-Ying Huang; En-Chao Li; Mei-Ling Feng (Journal of Hazardous Materials, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Aminophenol - ethylenediamine-based carbon dots as antioxidant nanozymes for multimodal protection against acute kidney injury - Zhenting Zhao; Jing Zhang; Mei Yang; Jiahao Huang; Zepeng Li; Mingzhen Zhang; Jianhui Li; Hongbao Li; Hua Wang; Chenguang Ding; Hongtao Jiang; Wujun Xue (Chemical Engineering Journal, 2026)

Pesticide beta-cypermethrin impairs endometrial decidualization and embryo implantation by suppressing autophagy through oxidative stress - Li-Qing Wang; Huang-Nian You; Qiong-Jun Xu; Wen-Jie Yu; Xiao-Mei Wu; Xiao-Qing Pang; Xiao-Xi Chen; Wen-Bin Du; Qian-Feng Qiao; Jing-Ai Li; Yu-Meng Zhou; Yong-Jiang Zhou (Chemico-Biological Interactions, 2026)

Study on Blast-Induced Crack Propagation in a Nine-Hole Model with Sequential Detonation Control - Da Mei; Junhong Huang; Xinping Li; Yi Luo; Tingting Liu; Chunneng Yang (Rock Mechanics and Rock Engineering, 2026)

Antimicrobial Mechanism of Temporin L Peptide Against Bacillus cereus from Fermented Sausage - Tiantian Yu; Fangyu Wang; Ibrahim A. Bakry; Qian Li; Tiange Li; Guangshan Zhao; Yongxia Cheng; Peijun Zhao; Mei Hu; Lianjun Song; Bangbang Zhao; Xianqing Huang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Highly sensitive m6A electrochemical biosensor based on laser-induced graphene electrodes functionalized with DNA tetrahedron/gold-antibody nanoparticle - Huiyan Cao; Xi Cheng; Li Huang; Haotian Zhang; Ziyi Liu; Wenjun Yang; Song-Mei Liu; Fang Wang (Analytica Chimica Acta, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Age-related metabolomic signatures and stroke susceptibility in a population-based cohort - Yanfeng Jiang; Qingxia Huang; Jincheng Li; Qinsheng Chen; Jialin Li; Zhenqiu Liu; Mei Cui; Chen Suo; Kelin Xu; Li Jin; Huiru Tang; Xingdong Chen (GeroScience, 2026)

The eastern branch fault model of the Tanlu Fault zone and its controlling effect on hydrocarbon accumulation: A case study of southern section of Bohai Sea - Ji-mei Deng; Shi-qiang Xia; Wen-hui Huang; Peng Wu; Gang Han; Hong Li (Applied Geophysics, 2026)

Scoparone alleviates cisplatin-induced acute kidney injury by inhibiting 5-lipoxygenase-mediated ferroptosis - Congcong Dai; Shuting Huang; Na Huang; Suwan Mu; Suwang Liu; Minhui Xie; Jing Mei; Yuhong Tang; Honghao Yu; Pengpeng Yue; Yong Li; Jun Ou (Toxicology and Applied Pharmacology, 2026)

Context-dependent reshaping of rhizosphere microbial communities by intercropping systems: A systematic analysis of 32 crop combinations - Feixue Li; Linna Ma; Jingyu Li; Chen Ye; Xinyue Mei; Siji Zhao; Yiwen Li; Yixiang Liu; Huichuan Huang; Xiang Li (Rhizosphere, 2026)

First fossil fruit of Spatholobus (Papilionoideae, Fabaceae) from East Asia - Yi-Shan Zhao; Zhen-Dong Cao; Jing-Nan Huang; Zi-Yi Li; Torsten Wappler; Zhen-Xian Zhang; Shu-mei Xiao; Wei-Yu-Dong Deng; San-Ping Xie (Review of Palaeobotany and Palynology, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Enhanced wastewater treatment performance in a two-stage pyrite-based denitrifying deep bed filter - Jun Ding; Feng Ling; Shu-Yang Tian; Wen-Bo Xie; Xiao-Cai Chen; Li Yu; Xu-Mei Li; Fa-Zhi Xie; Wei-Hua Li; Tong-Zhan Xue; Hou-Yun Yang; Xian-Huai Huang (Journal of Environmental Chemical Engineering, 2026)

Hydrophobic deep eutectic solvents for highly efficient n-hexane capture - Yan Zhao; Yanlong Xu; Anna Mei; Yingzhe Chen; Chee Sien Wong; Zhao Huang; Yulong Shan; Jianmeng Chen; Qian Li; Dong-Zhi Chen (Journal of Environmental Sciences, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

The physicochemical and simulated digestive characteristics of yam flours processed by different thermal processing methods - Ya Huang; Mei Deng; Xuchao Jia; Lihong Dong; Fei Huang; Qin Ma; Mingwei Zhang; Shan Liang; Yanxia Chen; Fengjuan Li; Ruifen Zhang (Food Chemistry, 2026)

Cultivar-type driven fertilization strategies to decouple the trade-off between wheat yield and grain protein in dryland systems - Xuemei Zhang; Junfeng Xu; Zikang Guo; Cui Huang; Xiaohan Li; Zhiyuan Gao; Jiachuang Fang; Chenrui Liu; Yulan Ding; Jian Hou; Zilin Wang; Yang Feng; et al. (Field Crops Research, 2026)

Synergistic phosphorus-carboxyl co-modification of dolomite for enhanced immobilization and long-term stabilization of Pb in acidic contaminated soils - Jiaxue Sun; Fanmin Zhu; Ronghui Zhang; Chongqing Mei; Shijie Zhao; Zhanbin Huang; Chuanfu Li (Environmental Research, 2026)

Exploring molecular-level rolling friction based on cyclodextrins for lubrication - Jiao Wang; Hao Cao; Wei You; Ding Xiao; Lan Sheng; Yuan Wang; Honggang Mei; Qing Bi; Xuedong Xiao; Yuping Wang; Guangfeng Li; Chenchen Wang; et al. (Carbohydrate Polymers, 2026)

Hyaluronic acid-based supramolecular peptide-drug conjugate prodrug nanosystems for precise multiple myeloma therapy - Xiangyu Deng; Qili Huang; Li Cao; Ran Luo; Wenyan Wang; Hongzhong Chen; Chendi Ding; Lina Su; Lin Mei (Carbohydrate Polymers, 2026)

Research and application of intelligent loading pattern search for pressurized water reactors - Peng Sitao; Wei Jinfeng; Yao Jianfan; Yang Shuoyan; Li Wenhuai; Yang Zhengyu; Huang Jie; Mei Gaohui; Huang Yunten; Zhao Changyoug; Yu Chao; Wang Ting; et al. (Annals of Nuclear Energy, 2026)

Clinical utility of metagenomic next-generation sequencing in precision diagnosis of infectious diseases: a retrospective study based on bronchoalveolar lavage fluid, blood, and cerebrospinal fluid - Congwen Shao; Jun Li; Chunyan Huang; Mei Tang; Junzhao Zeng; Wenyan Zhou; Dandan Zhang; Guansheng Zeng; Jianwei Wang; Tian Hua; Chuhang Zhong; Jie Hu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Lignanamides, alkaloids, and other constituents from stems of Tinospora crispa - Yi-Yang Yuan; Xiang-Hong Chen; Tian Gao; Jun Li; Xian-Ju Huang; Hui Xiong; Zhi-Nan Mei; Yu Chen; Guang-Zhong Yang (Natural Product Research, 2026)

Endophyte-engineered plant immunity: A post-GMO strategy for programmable crop defense - Fan Zhang; Jing Zheng; Xinyun Xie; Mengru Tang; Hongyang Li; Linyin Zuo; Lu Zheng; Hao Liu; Junbin Huang; Zhinan Mei; Xiao-Lin Chen (Molecular Plant, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Electron buffering by carbon dots enhances H2 activation and selective aldehyde hydrogenation over Cu/Al2O3 catalysts - Feifei Mei; Chenyang Shen; Mingyang Deng; Jun Yao; Yue Huang; Fengfeng Li; Mingyang Deng; Xuefeng Guo; Weiping Ding (Chemical Engineering Journal, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

A preference study for applying mHealth to improve the quality of cervical cancer screening management from a supply and demand perspective: a discrete choice experiment - Wei Jin; Xue Wang; Yingxuan Fan; Chunxia Huang; Nian Zhang; Yamei Wei; Xiaoling Ma; Jiesong Wang; Yaxin Li; Huaimiao Jia; Mei Zhang (Cancer Causes & Control, 2026)

Multifaceted environmental footprints of spent coffee grounds valorization: from waste management to fuel and material production - Shuying Huang; Lan Wang; Jingwen Wang; Xi Tian; Mei Li; Xinyi Zhang; Dungang Gu; Tingting Hu; Rui Liu; Guanghui Li; Jiaqi Lu (Resources, Conservation and Recycling, 2026)

Integrated nanoarchitectonics of porous carbon with high specific surface area and liquid fertilizer from distiller's grains by hydrothermal process - Yao Zhao; Zhanglin Liu; Binglin Wang; Jinguang Hu; Mei Huang; Li Zhao; Dong Tian; Jinsong He; Jianmei Zou; Fei Shen (Biomass and Bioenergy, 2026)

Linking soil organic carbon and viral communities in alpine grasslands - Wenyin Wang; Xiaochun Wang; Lingyan Qi; A. Allan Degen; Mei Huang; Binyu Luo; Zheru Zhang; Tianyun Qi; Shuai Qi; Sisi Bi; Chunying Li; Jinfeng Yue; et al. (Plant and Soil, 2026)

A new method for solving the magnetotelluric forward problem in geophysics - Shuai Zhang; Mei Huang; Yanting Cheng; Fawang Ye; Yaodi Li; Yiyuan Du; Shiju Jin; Yuanyuan Zhao; Fenglei Niu (Annals of Nuclear Energy, 2026)

Pseudosparassis yunnanensis, gen. et sp. nov. (Sclerotiniaceae, Helotiales, Ascomycota) from Yunnan Province, Southwestern China - Yuan-Hao Ma; Qi Zhao; Li-Mei Huang; Ping Liu; Hong-Mei Chai; Yong-Chang Zhao; Hong-Li Su; Ishika Bera; Wei-Min Chen (Mycological Progress, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Holocene climate optimum moisture variability in the monsoon marginal zone of northern China revealed by multi-proxy stalagmite records - Shouyi Huang; Yanjun Cai; Gang Xue; Xinhui Zhang; Mei He; Ruoxin Li; Yingying Wei; Le Ma; Xing Cheng; Haiwei Zhang; Hai Cheng (Global and Planetary Change, 2026)

Microbial community dynamics in spontaneous fermentation of Vitis quinquangularis Rehd. Wine across Southwest China: Correlations with volatile compounds - Guopin Chen; Qiufeng Huang; Su Ding; Yafang Cheng; Mei Lu; Xiaoqi Zhou; Jing Huang; Yu Huang; JingXi Guan; Muming Cao; Wei Li (Food Research International, 2026)

Quality enhancement of frozen dough steamed bread by Sanxan: A study on multi-stage regulation of gluten-starch matrix - Haojia Zhu; Heqiao Qian; Jie Li; Hanzhang Hao; Ying Huang; Shenying Zhang; Yingxue Che; Mei Liu; Ying Liang; Xueling Zheng; Chong Liu; Limin Li (Food Hydrocolloids, 2026)

Enhancing flame retardancy, mechanical strength, and self-healing property of waterborne polyurethane via diselenide and modifying Al/Zn@ phytic acid - Haonan Chen; Wenhua Zeng; Jiangyang Mei; Zhexian Mao; Kun Huang; Guozheng Li; Wang Zhong; Yong Jin (Chemical Engineering Journal, 2026)

Topology-Adaptive Graph Attention Networks coupled with radial basis functions: A novel framework for hydraulic conductivity inversion in unstructured meshes - Zhao Guo; FuTian Ren; DanBing Mei; Fan Liu; ZengHui Li; XiaoWei Lu; Lei Huang (Advances in Water Resources, 2026)

The DNA mismatch repair protein Msh4 is essential for meiosis of male but not for female in zebrafish - Yankun Guo; Yunbang Zhang; Yihui Mei; Yuwei Huang; Yuxuan Zheng; Nan Zhang; Yuxin Jiang; Hanjun Jiang; Zijie Zhang; Angxiao Li; Jinchang Fan; Katsutoshi Arai; et al. (Chromosome Research, 2026)

A multi-layer coupling framework for hydrodynamic simulation of underground station flooding - Dong-Mei Zhang; Hai-Yun Li; Wen-Ding Zhou; Si-Rui Chen; Zhong-Kai Huang (Tunnelling and Underground Space Technology, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Adjuvant-metal-ion-chelating PTEN mRNA with cell-membrane-coating augments the immune sensitivity for precise cancer immunotherapy - Mengyu Guo; Jin-Cheng Guo; Haodong Yao; Fene Gao; Lina Zhao; Lu Cai; Xuan Fan; Lin Bao; Xin Li; Xiaoyu Zhang; Mingdi Hu; Jie Mei; et al. (Science Bulletin, 2026)

Two unprecedented 2-(2-phenylethyl)chromone dimers from the Cambodian agarwood of Aquilaria crassna - Yan Huang; Hao Wang; Wen-Li Mei; Hui-Qin Chen; Fei Wu; Yan-Mei Wei; Wen-Ming Cheng; Hao-Fu Dai (Phytochemistry Letters, 2026)

Process parameter optimization for greenhouse gas mitigation during green-waste composting and mechanistic insights from microbe–environment networks in treatments with contrasting outcomes - Xiaowen Li; Min Cao; Wenyuxin Huang; Hao Mei; Pan Luo; Ping Ma; Junhao Zhang; Weiqin Zhu; Miaomiao He; Ying Ding (Journal of Cleaner Production, 2026)

Fast solar-heating sponge with TEMPO-modified PDA coating for rapid recovery of highly-viscous oil on water - Jichen Huang; Xiaoyun Sun; Jinfeng Mei; Xudong Zheng; Zhongyu Li (Journal of Environmental Chemical Engineering, 2026)

The secreted in xylem protein Foc4-SIX13 of Fusarium oxysporum f. sp. cubense race 4 targets the banana Nudix hydrolase and contributes to its virulence - Wenjing Chen; Jiamin Zheng; Jiahui Wu; Rujing Zeng; Zheng Li; Yinghua Huang; Tom Hsiang; Handa Song; Mei Luo; Zhangyong Dong (Fungal Biology, 2026)

Effects of recombinant carrot antifreeze protein concentrations on frozen dough and bread: Insights into dynamic changes of water and ice crystals - Ying Huang; Shenying Zhang; Haojia Zhu; Caiyun Liu; Zichen Huang; Hanzhang Hao; Yingxue Che; Mei Liu; Ying Liang; Xueling Zheng; Chong Liu; Limin Li (Food Chemistry, 2026)

Effects of taurine on immunity and ammonia metabolism in large-scale loach under ammonia stress - Ruo-Yu Zhou; Lu Chen; Meng-Yang Hu; Mu-Xi Li; Yu-Xuan Fei; Mei Huang; Yun-Long Zhang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Metallic-phase MoS2 nanosheets boost polysulfide redox kinetics to high-performance polysulfide-based flow batteries - Ruiyu Liu; Su Yan; Xin Huang; Weizhe Xiang; Jian Xu; Zhizhao Xu; Mei Ding; Binglei Liu; Hongtai Li; Xiaolei Huang; Shengqi Chu; Guangmin Zhou; et al. (Chemical Engineering Journal, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Phthalocyanine-based prodrug with H₂S-triggered domino cascade for photodynamic and multiple-mechanism synergistic anti-metastatic therapy - Mengyu Yao; Qi-Qi Yang; Huang-Hao Tang; Xue-Yan Li; Wei Xie; Chao Wang; Song Yang; Xingshu Li; Mei-Rong Ke; Jian-Dong Huang (Chemical Engineering Journal, 2026)

Hierarchical Framework for Reservoir Co-management: A Cross-scale Reservoir Dispatch Paradigm Balancing Energy and Morphogenic Flow Needs - Hong Zeng; Tian-Yao Zhang; Yi-Ming Liao; Guang-Wen Ma; Ji-Dong Li; Wei-Bin Huang; Yan-Mei Zhu; Shi-Jun Chen (Water Resources Management, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Analysis of the effect of LFR bending fuel assembly on thermal–hydraulic characteristics - JiTong Sun; Mei Huang; YaoDi Li; AoNan Li; YanTing Cheng (Annals of Nuclear Energy, 2026)

Phyllosphere to soil: How long-term fencing reshapes grassland microbial community construction and the functional genes - Jian Li; Yu Zhu; Daniel F. Petticord; David W. Frey; Lijie Huang; Ming-Kang Jin; Michiel Op de Beeck; Quan-Hui Ma; Shu-Huan Jin; Hong Ying; Xi-Mei Xue; Ling Wang; et al. (Agriculture, Ecosystems & Environment, 2026)

Determination of reference point for Sheshan SLR telescope using self-driven prism system - Zhikang Wang; Zhibin Zhang; Bin Wang; Shuzhen Yuan; Zhipeng Mei; Xiaohui Ma; Liangquan Jia; Yong Liu; Haifeng Zhang; Si Qin; Li Zhang; Chengli Huang; et al. (Advances in Space Research, 2026)

Unraveling the coloration pattern of male bitterling (Rhodeus ocellatus) with implications for ornamental fish industry - Jing Huang; Haitao Wang; Yongqin Zhang; Mei Wang; Qian Peng; Xing Guo; Jiaxin Li; Yuanyuan Liu; Kaiyue Zhao; Guangjing Zhang; Jinhui Liu; Yamei Xiao (Aquaculture, 2026)

Caseazins R−Y, cytotoxic podocarpane diterpenoids from Casearia kurzii - Xue-Wen Wu; Qiong Wei; Xia Pu; Chun-Mei Cha; Rui Li; Yin-Qiao Huang; Rui-Han Zhang; Xiao-Li Li; Hong-Liang Li; Wei-Lie Xiao (Phytochemistry, 2026)

Characterisation of microbial succession and exploration of the stability maintenance strategy of phage community on microbes in radish paocai - Menglu Yang; Yuli Huang; Jiaqi Liu; Guangqiang Wang; Yuan Mei; Lihong Ge; Qing Du; Huajia Li; Nan Zhao (International Journal of Food Microbiology, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

The soil plastisphere: A hotspot for arsenic methylation regulated by microplastic polymer types - Kaimei Zhang; Wei Feng; Qingnan Huang; Williamson Gustave; Yimin Cai; Da Ouyang; Mei Li; Xianjin Tang; Haibo Zhang; Ting Guo (Environmental Research, 2026)

Bioturbation experiment reveals the negative impact of physical damage and shading on the growth of Vallisneria spinulosa S. Z. Yan, a rapidly declining submerged macrophyte in the lower Yangtze region - Min Guo; Zhe Li; Chengfeng Luo; Shaoxia Xia; Yunzhe Huang; Geng Huang; Chenglin Li; Leiqiang Gong; Zonghua Zhang; Yong Mei; Hao Luo; Xiubo Yu; et al. (Hydrobiologia, 2026)

Long-term settlement prediction of shield tunnel interval considering spatial information - Dong-Mei Zhang; Zhao-Geng Chen; Yi-Ming Shen; Zhong-Kai Huang; Xiao-Chuang Xie; Xiao-Yang Guo; Deng-Fei Yan; Yong-Bo Li (Tunnelling and Underground Space Technology, 2025)

Uncertainty-aware deep distributed reinforcement learning for autonomous navigation of unmanned surface vehicles in complex environments - Mei Huang; Xiaowei Li; Zhihui Li; Dan Zhang; Yaoran Chen (Ocean Engineering, 2025)

A novel 450 nm blue laser-mediated sinoporphyrin sodium-based photodynamic therapy inactivates Cutibacterium acnes through stress-mediated metabolic alterations - Hengtong Fan; Zejun Ren; Shuqi Chen; Tingting Huang; Guoxiong Liu; Yashou Guo; Yan Zheng; Yifan Cheng; Xing Li; Yibo Mei; Yuhang Chen; Huihui Tuo; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

DeepSANet: A deep learning approach for hierarchical geographical source attribution of Salmonella - Shan Liang; Shaohui Mei; Jiahao Ji; Bingkui Li; Mingyuan Xu; Miaomiao Chen; Yawen Huang; Yuxin Zheng; Di Chen; Xiangyu Deng; Shaoting Li; Hongmei Zhang (Food Research International, 2025)

A novel reversible-responsive ratiometric fluorometry based on an anthracene-based imidazolium ionic liquid and Eu3+-based lanthanide coordination polymers for selective sensing tetracycline in foods and waters - Xiaoqi Jiang; Jingcheng Huang; Mengting Li; Linjin Li; Yinuo Chen; Jiangfei Chen; Junlun Zhu; Xuedong Wang; He Mei (Food Chemistry, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

Natural compound rhein-based bimetallic nanosheets to induce ferroptosis and activate STING pathway for enhanced cancer immunotherapy - Chang Li; Tiancheng Xie; Xilong Mei; Yu Wen; Mi Huang; Hu Guo; Ping Lu; Xiaoxin Yang; Jun Liu (Chemical Engineering Journal, 2025)

Mechanically robust and rapidly self-recovering hyaluronic acid-based conductive hydrogels via fully physical double-network crosslinking for sensitive strain sensors - Ye-Xiong Huang; Mei-Dan Luo; Dewei Ye; Jinmin Li; Ku Shu; Xian-Ping Chen; Kai Zheng (Chemical Engineering Journal, 2025)

The Holocene stalagmite trace element and Sr isotope records from Central China and the inferred hydroclimate changes - Yuting Wu; Yanjun Cai; Fugui Xiao; Mei He; Shouyi Huang; Xiangkun Zhai; Ruoxin Li; Gang Xue; Hanying Li; Chunlei Zong; Hai Cheng (Chemical Geology, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Accuracy analysis of different numerical methods on thermal stratification prediction of liquid metal - Shuai Zhang; Yunqing Bai; Wenbo Li; Ming Jin; Tinyu Li; Mei Huang; Qiaoyan Chen; Fenglei Niu (Annals of Nuclear Energy, 2025)

High-throughput wheat seedling phenotyping via UAV-based semantic segmentation and ground sample distance driven pixel-to-area mapping - Honghao Zhou; Qing Li; Bingxi Qin; Haijiang Min; Shaowei Liang; Xiao Wang; Jian Cai; Qin Zhou; Mei Huang; Dong Jiang; Yingxin Zhong; Jiawei Chen (Computers and Electronics in Agriculture, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Phylogenomic insights into incomplete lineage sorting and hybridization in early-diverging eudicots - Yu-Xin Liu; Xiao-Mei Huang; Wen-Chuang He; Andrey S. Erst; Kun-Li Xiang; Wei Wang (Molecular Phylogenetics and Evolution, 2025)

Interactive effects of soil characteristics and polymer types reveal patterns of denitrifying bacteria enrichment in the soil plastisphere - Ting Guo; Shunyin Huang; Xiangyi Jin; Mengyao Xing; Williamson Gustave; Yimin Cai; Da Ouyang; Mei Li; Yanjiang Cai; Haibo Zhang (Journal of Hazardous Materials, 2025)

Smoldering heterogeneous oily sludge: Key influencing factors - Yi Lin; Zehua Luo; Fuli Li; Chih-Huang Weng; Yanru Hao; Na Liu; Mei Hong (Journal of Cleaner Production, 2025)

Development of a rapid method for the determination of the spatial distribution of protein in wheat grain using mature resin section and image processing algorithm - Hengtong Wang; Haijiang Min; Minghao Gao; Han Zhong; Chuan Zhong; Zenan Ban; Qin Zhou; Xiao Wang; Jian Cai; Qing Li; Mei Huang; Dong Jiang; et al. (Journal of Cereal Science, 2025)

Emergence and genomic characterization of Vibrio parahaemolyticus serotype O10:K4 from seafood-linked diarrheal cases in Zhejiang, China (2016–2023) - Jiewen Huang; Zhen Zhang; Qingtian Li; Jiancai Chen; Lingling Mei; Xiaojuan Qi; Lili Chen; Junyan Zhang; Chao Lv; Min Li; Honghu Chen; Yanjun Zhang; et al. (Food Research International, 2025)

Polystyrene nanoplastics impair endometrial decidualization via cell cycle arrest and JNK-MAPK pathway-mediated oxidative stress in early pregnant mice - Jing-Ai Li; Li-Qing Wang; Qiong-Jun Xu; Xiao-Mei Wu; Xiao-Qing Pang; Jin-Xin He; Qian-Feng Qiao; Huang-Nian You; Yan-Chun Wu; Yong-Jiang Zhou (Food and Chemical Toxicology, 2025)

Failure mechanism of rock tunnels subjected to combined reversed fault dislocation and subsequent seismic excitation - Dong-Mei Zhang; Li Guo; Zhong-Kai Huang; Yi-Yao Shen; Kyriazis Pitilakis (Computers and Geotechnics, 2025)

High crystalline VSe2@PANI collaborating with ether electrolyte to construct efficient sodium-ion storage interface - Dejian Liu; Sixing Xie; Zijian Zhan; Yuqi Mei; Ruiguang Li; Cheng Zheng; Shaoming Huang (Chemical Engineering Journal, 2025)

Synergistic dual-Lewis sites in cobalt-doped Fe3S4 for enhanced hydrogen peroxide activation and contaminant degradation - Li-Ping Jin; Fan Zhou; Qin Liu; Su-Qin Wang; Meng-Meng Zeng; Xin-Yu Huang; Li Liu; Xiao-Han Yu; Mei-Feng Wu; Jian-Ping Zou (Chemical Engineering Journal, 2025)

The spatial diversity of secondary organic carbon aerosols at the city level: insights from explainable machine learning - Xiaojian Xu; Cheng Wu; Chenglei Pei; Mei Li; Chunlei Cheng; Menghua Lu; Zhijiong Huang; Baoling Liang; Xinkun Fang; Mengxi Ye; Dui Wu (Atmospheric Environment, 2025)

Associations of changes in social isolation and loneliness with all-cause mortality among older adults: a prospective cohort study - Qing-Mei Huang; Si-Tong Wei; Zhi-Hao Li; Yue-Bin Lv; Xiao-Ming Shi; Chen Mao (GeroScience, 2025)

New lignans from Phyllanthodendron dunnianum - Li Xu; Jian-Bing Tan; Yu-Ting Zheng; Zi-Huan Sang; Si-Yu Qin; Yuan-Tao Huang; Mei-Fang Li; Zhen-Xing Zou (Natural Product Research, 2025)

Oxymatrine possibly inhibits differentiation and maturation of oligodendrocytes in the remyelination of the toxin-induced demyelination animal model - Mei Li; Fei Huang; Jian Song; Renzhang Liang; Zhongwei Zhou; Yinglan Lin; Lili Hu; Jinghai Gu; Hua Yang; Shaozhang Hou; Huisheng Ma; Peng Wang (Metabolic Brain Disease, 2025)

Two unprecedented 2-(2-phenethyl)chromone derivatives with anti-Helicobacter pylori and anti-inflammatory activities from agarwood of Aquilaria crassna - Xiao-Hong Li; Hao Wang; Wen-Li Mei; Wen-Hua Dong; Jun Zeng; Sheng-Zhuo Huang; Hui-Qin Chen; Yan-Mei Wei; Fei Wu; Zhi-Yong Guo; Hao-Fu Dai (Phytochemistry Letters, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Phosphorus-functionalized dolomite for cadmium immobilization in water systems and acidic soil remediation: Mechanistic insights and scale validation - Jiaxue Sun; Chongqing Mei; Fanmin Zhu; Zhanbin Huang; Chuanfu Li (Journal of Environmental Chemical Engineering, 2025)

Dual-sulfur defects decorated 1T-WS2/Cd0.5Zn0.5S heterojunctions for boosted photocatalytic hydrogen evolution - Mei Dong; Wenjun Li; Liang Geng; Ruixue Huang; Hongli Han; Yuan Liu (Journal of Environmental Chemical Engineering, 2025)

The interactions, impacts, and removal strategies of microplastics (MPs) and antibiotic resistance genes (ARGs) in aquatic environments, particularly in wastewater treatment plants (WWTPs) - Ying Wang; Xin-Rui Zhang; Min-Min Qiang; Zheng Huang; Xin-Tao Liu; Run-Mei Li; Zi-Yue Li; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Chemical Engineering, 2025)

A 3D point cloud and deep learning based automated process for quantifying multi-scale phenotypes in sliced bread - Honghao Zhou; Jungao Zhang; Qin Zhou; Xinru Wang; Haijiang Min; Bingxi Qin; Shaowei Liang; Xiao Wang; Yingxin Zhong; Jian Cai; Mei Huang; Qing Li; et al. (Food Research International, 2025)

Effect of cold plasma modification on bacterial cellulose and its dispersion behavior in chitosan-based matrix - Hui-mei Liu; Yao-yao Wang; Xiangzhen Ge; Yun Chen; Xi-guang Ye; Yong Hu; Mengfan Li; Chao Huang; Dong-mei Li (Food Bioscience, 2025)

Preparation of highly charged zwitterionic nanochitin for stabilizing Pickering emulsions - Qiannuo Li; Lei Zhang; Xue Gao; Zhongshuai Gao; Mei Cui; Renliang Huang; Rongxin Su (Carbohydrate Polymers, 2025)

The role of N6-methyladenosine (m6A) modification in plants - Cui-Xian Qin; Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Miao Wang; You-Qiang Pan; Li Zhou; Bao-Qing Zhang; Jian-Hui Zhou; Dong-Liang Huang (Theoretical and Applied Genetics, 2025)

Multi-omic-based classification for identifying optimal neoadjuvant treatment strategies for high-risk early-stage breast cancer - Fei Ji; Xianzhe Chen; Ciqiu Yang; Liulu Zhang; Mei Yang; Jieqing Li; Hongfei Gao; Teng Zhu; Minyi Cheng; Yitian Chen; Hao Peng; Jin Wang; et al. (Science China Life Sciences, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Generation of donor-derived spermatozoa by cross-subfamily transplantation of purple loach (Leptobotia taeniops) spermatogonia into triploid loach (Misgurnus anguillicaudatus) - Yihui Mei; Min Guan; Yuxuan Zheng; Yunbang Zhang; Qingshan Li; Yasmeen Gul; Yankun Guo; Yuxing Jiang; Wenqi Chang; Yuwei Huang; Nan Zhang; Jian Gao; et al. (Fish Physiology and Biochemistry, 2025)

Extensive Introgression Failed to Erode Species Boundaries Among Multiple Sympatric Closely Related Species of Roscoea - Hong‐Fan Chen; Ryan Andrew Folk; Ya‐Li Wang; Wen‐Jing Wang; Guo‐Jun Shao; Mei‐Yuan Huang; Xiang‐Qin Yu; Li Li; Jian‐Li Zhao (Molecular Ecology, 2025)
How species boundaries are maintained among sympatric closely related species experiencing gene flow is a puzzling question in evolutionary biology. Although introgression is commonly documented, the dynamics and gene function of introgression have rarely been explored to probe why frequent introgression does not necessarily destroy species boundaries in sympatry. In this study, we employ whole‐genome resequencing data to examine introgression among five closely related species of Roscoea that coexist in a ‘sky island’ with seventeen distinct morphological traits. Our findings reveal that introgression has led to the phylogenomic discordance between nuclear and chloroplast genomes among these morphologically distinct species. Additionally, introgression is predominantly asymmetrical in both intensity and gene function, particularly concerning recombination. Notably, the majority of gene functions associated with introgressed loci are unrelated to reproductive processes. Our results suggest that closely related species with incomplete allele assortment can coexist despite theoretical predictions, highlighting the semipermeable nature of species boundaries as reproductive isolation develops. This provides a critical conceptual framework for understanding the interplay between introgression and species persistence. Our finding offers insights into how related sympatric species boundaries can be maintained in the face of frequent asymmetrical gene introgression.

Evidence for cognitive compensation mechanism in the postoperative delirium: a prospective multi-modal neuroimaging cohort study - Guo-Bin Zhang; Hao-Yi Li; Jia-Mei Lv; Xiao-Kang Zhang; Yong-Gang Wang; Yun-Yun Duan; Hong-Yan Chen; Zhi-Zheng Zhuo; Ya-Ou Liu; Hua-Wei Huang (Brain Imaging and Behavior, 2025)

Seaweed polysaccharides as potential Prebiotics: Rationale, factors, Prebiotic activity manifestations, gut health mechanisms and extraintestinal impacts - Qianmin Lin; Li Zhong; Mei Zeng; Supaluck Kraithong; Xuewei Xia; Weiyang Kuang; Qingqing Wang; Riming Huang (Trends in Food Science & Technology, 2025)

Artemsieverlides A–M, diverse sesquiterpenoid dimers with antihepatic fibrosis activity isolated from Artemisia sieversiana based on molecular networking - Wei Dong; Tian-Ze Li; Xiao-Yan Huang; Yan-Mei Weng; Chang-An Geng; Ji-Jun Chen (Phytochemistry, 2025)

Phthalocyanine-based nanosensitizers for enhanced sonodynamic therapy activity of hypoxic tumor with dual apoptosis/ferroptosis pathways - Xue-Yan Li; Jin Liu; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Nanocatalytic-phytoremediation synergistic strategy: Functional carbon nanodots enhancing nonylphenol biodegradation in contaminated soil - Qiong Chen; Junjie Huang; Junbo Zhou; Lanxuan Sun; Jianing Yang; Qiuyu Shu; Yiwen Sun; Juan Li; Mei Yan (Journal of Hazardous Materials, 2025)

Sheep and rapeseed cake manure promote antibiotic resistome in agricultural soil - Chenyu Huang; Tianyu Wang; Weibin Chen; Jiao Wang; Minrong Cui; Conglai Zheng; Mengting Qiu; Mei Shan; Baotong Li; Luqing Zhang; Yunlong Yu; Lihui Xu; et al. (Journal of Hazardous Materials, 2025)

Activation of molecular oxygen over MnOX/CeO2 for catalytic wet air oxidation of high-concentrated phenolic pollutants - Li Zhao; Haiping Mao; Yuanjing Lai; Jinsong He; Dong Tian; Mei Huang; Yongjia Lei; Fei Shen; Jianmei Zou (Journal of Environmental Management, 2025)

Synergistic inhibition of Maillard reaction hazards: Multifunctional hydrocolloids enable healthier air-fried beef patties with reduced heterocyclic amines and AGEs - Hongfei Du; Huang Zhang; Zixin Zhang; Zihan Yuan; Maiquan Li; Lei Zhou; Yan Liu; Aihua Lou; Mei Li; Ye Jiao; Qingwu Shen; Chaoyi Xue; et al. (Food Chemistry, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

AdaptiveGS: an explainable genomic selection framework based on adaptive stacking ensemble machine learning - Zhen Yang; Mei Song; Xianggeng Huang; Quanrui Rao; Shanghui Zhang; Zhongzheng Zhang; Chenyang Wang; Wenjia Li; Ran Qin; Chunhua Zhao; Yongzhen Wu; Han Sun; et al. (Theoretical and Applied Genetics, 2025)

Dynamic Characteristics and Energy Dissipation Laws of Reinforced Porous Coral Reef Limestone - Da Mei; Xiaoqing Wei; Yi Luo; Shangyuan Chen; Xinping Li; Junhong Huang; Chunneng Yang (Rock Mechanics and Rock Engineering, 2025)

Compartment-specific core microbiomes and functions in rice - Linna Ma; Yusha Bai; Xiang Li; Jingyu Li; Feixue Li; Yan Yue; Yingguang Li; Jingwen Guo; Chen Ye; Xinyue Mei; Fei Du; Yixiang Liu; et al. (Plant and Soil, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Establishment of an efficient in vitro regeneration protocol for Dendrobium primulinum Lindl. by one-step seedling formation - Cheng-Li Liu; Jie-Mei Deng; Shun Peng; Heng-Yu Huang; Fu-Rong Xu (In Vitro Cellular & Developmental Biology - Plant, 2025)

Influence of distillery sewage sludge application placement methods on microbial community functions in sorghum rhizosphere: Focus on nitrogen and phosphorus cycling - Hongpei Lu; Yonggui Wu; Youfa Luo; Jiayi Yuan; Yajiao Huang; Peng Zhang; Xingying Li; Mei Zhu; Qi Zhang; Yibin Qiang; Ningning Wang (Applied Soil Ecology, 2025)

A portable point-of-care testing platform for rapid and sensitive miRNA-21 detection for heart failure diagnosis - Qian Kai Lin; Wen Qing Sun; Bo Zhang; Qiao Ling; Yan Qian; Cheng Zhi Huang; Chun Mei Li; Na Wang (Analytica Chimica Acta, 2025)

Identification, expression analysis, and functional verification of three opsin genes related to the phototactic behaviour of Ostrinia furnacalis - Mei Huang; Jian‐Yu Meng; Xue Tang; Long‐Long Shan; Chang‐Li Yang; Chang‐Yu Zhang (Molecular Ecology, 2025)
Ostrinia furnacalis is a disreputable herbivorous pest that poses a serious threat to corn crops. Phototaxis in nocturnal moths plays a crucial role in pest prediction and control. Insect opsins are the main component of insect visual system. However, the inherent molecular relationship between phototactic behaviour and vision of insects remains a mystery. Herein, three opsin genes were identified and cloned from O. furnacalis ( OfLW , OfBL , and OfUV ). Bioinformatics analysis revealed that all opsin genes had visual pigment (opsin) retinal binding sites and seven transmembrane domains. Opsin genes were distributed across different developmental stages and tissues, with the highest expression in adults and compound eyes. The photoperiod‐induced assay elucidated that the expression of three opsin genes in females were higher during daytime, while their expression in males tended to increase at night. Under the sustained darkness, the expression of opsin genes increased circularly, although the increasing amplitude in males was lower when compared with females. Furthermore, the expression of OfLW , OfBL , and OfUV was upregulated under green, blue, and ultraviolet light, respectively. The results of RNA interference showed that the knockout of opsin genes decreased the phototaxis efficiency of female and male moths to green, blue, and ultraviolet light. Our results reveal that opsin genes are involved in the phototactic behaviour of moths, providing a potential target gene for pest control and a basis for further investigation on the phototactic behaviour of Lepidoptera insects.

Recycling paper packaging waste into Fe-biochar pellet catalyst for tetracycline degradation via peroxymonosulfate activation - Li Zhao; Kangting Du; Mei Huang; Dong Tian; Jinsong He; Yongjia Lei; Yan Liu; Guochun Lv; Jianmei Zou; Fei Shen (Environmental Research, 2025)

Generation of human-induced pluripotent stem cells from a patient with Beckwith–Wiedemann syndrome - Mei Tang; Jiafan Lei; Congwen Shao; Wenyan Zhou; Min Xiong; Min Huang; Chunyan Huang; Fei Wang; Jun Liu; Jun Li; Xueqing Xu (Human Cell, 2025)

Anti-inflammatory sesquiterpenoids from Chloranthus japonicus - Wei-Jiao Feng; Pei-Zhi Huang; Li-Mei Zhang; Qian Ma; Hong-Yu Hu; Yue Gu; Ya Li; Kun Gao (Phytochemistry, 2025)

Three new polyketide metabolites from the endophytic fungus Trichoderma protrudens of Hibiscus tiliaceus - Yan-Mei Wu; Jing-Ya Mo; Yong-Yan Mei; Quan Liu; Yuan-Yuan Huang; Bei Zhou; Yi-Hang Li; Yan-Chun Wu; Jing-Quan Yuan (Phytochemistry Letters, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Hg0 to Hg2+ via photocatalysis by Bismuth-based photocatalysts: A review - Yifan Liu; Hengzhong Chen; Wenquan Zhou; Wencai Qian; Kai Huang; Xiaojing Liu; Mei Ma; Yang Ling; Jiang Wu; Fangqin Li (Journal of Environmental Chemical Engineering, 2025)

A novel, ridged enlarging lateral space drip irrigation pattern (ReDiP) for high- yield and WUE spring wheat in Xinjiang, China - Liulong Li; Zijian Wang; Wenliang Wan; Zhaofeng Li; Jian Cai; Qin Zhou; Mei Huang; Yingxin Zhong; Xiao Wang; Dong Jiang (Field Crops Research, 2025)

Multi-functional edible coatings tailored with nanocellulose for perishable fruits - Lei Zhang; Mei Cui; Huan Tong; Jiaqi Zhang; Qiannuo Li; Xue Gao; Wei Qi; Hon Loong Lam; Renliang Huang; Rongxin Su (Carbohydrate Polymers, 2025)

Molecular characterization and validation of adult-plant stripe rust resistance genes in Yunnan hulled wheat (Triticum aestivum ssp. yunnanense King) - Linyu Huang; Xinyu Wang; Yan Yan; Li Long; Qiushuo Li; Yuexue Wang; Yongjing Liu; Hao Li; Zhien Pu; Wei Li; Qiantao Jiang; Jian Ma; et al. (Theoretical and Applied Genetics, 2025)

Pore space optimization of hybrid ultramicroporous material for exceptional one-step C2H4 purification from C2H2/CO2/C2H4 mixture - Hong-Xiang Nie; Hong-Wei Chen; Ting Wang; Hongliang Huang; Qiang Gao; Mei-Hui Yu; Jian Zhu; Li-Bo Li; Zhenjie Zhang; Ze Chang; Xian-He Bu (Chemical Engineering Journal, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Establishment of virus-induced gene silencing in Euphorbia lathyris L. and its application in casbene synthase (CBS) gene functional analysis - Wei Lyu; Mei Tian; Long Huang; Bi Wang; Pirui Li; Wanli Zhao; Linwei Li; Xu Feng; Shu Xu; Yu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A new sesquiterpene from endophytic fungus Colletotrichum sp. B-89 - Ke-tao Zhang; Bing Zhang; Zhi-pu Huang; Yu-xiao Xu; Xiao-rong Xu; Si-heng Li; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2025)

Three new metabolites from the endophyte Fusarium proliferatum T2-10 - Jian-Bing Tan; Wei-Wei Peng; Mei-Fang Li; Feng-Hua Kang; Yu-Ting Zheng; Li Xu; Si-Yu Qin; Yuan-Tao Huang; Zhen-Xing Zou (Natural Product Research, 2025)

circEgg inhibits BmCPV infection by regulating the transition between H3K9me3 and H3K9ac - Qunnan Qiu; Xinyu Tong; Min Zhu; Zhe Liu; Mei Yin; Shutong Jiang; Liuyang Li; Yuqing Huang; Yongjie Feng; Xiaolong Hu; Chengliang Gong (Pesticide Biochemistry and Physiology, 2025)

Cooperation of Lactoplantibacillus plantarum and polyethylene microplastics facilitated the disappearance of tetracycline during anaerobic fermentation of whole plant maize - Yubo Zhang; Pan Wang; Yu Tang; Chaosheng Liao; Xiaolong Tang; Pai Hou; Cheng Chen; Xiaokang Huang; Guangrou Lu; Lin Li; Mingjie Zhang; Fuxiang Li; et al. (Journal of Hazardous Materials, 2025)

Fulfilling the negative emission effect of hydrothermal CO2 utilization through process optimization and supply chain decarbonization - Jingwen Wang; Shuying Huang; Mei Li; Jing Xu; Fangming Jin; Yang Yang; Heng Zhong; Chunling Wang; Guanghui Li; Jiaqi Lu (Journal of Cleaner Production, 2025)

Sludge gasification: Mineral behaviours and the high-value utilisation of gasification ash - Weiwei Zhang; Ruipeng Li; Youqing Wu; Shiyong Wu; Sheng Huang; Yanyang Mei; Xiaoping Wen; Anchao Zhang (Journal of Environmental Management, 2025)

Regenerable AgNPs-CdSNWs/Nanofilm as SERS substrates for sensitive detection of carbamate pesticides - Yutong Huang; Yan Luo; Xiaoqing Zhang; Shanglin Li; Mei Liu (Food Chemistry, 2025)

Functionalized dendritic memristor of Pt/MoS2@LCO-PVA/Si for Mimicking synaptic behavior - Xueli Geng; Qin Gao; Jiangshun Huang; Juan Gao; Pengzhan Li; Yihang Liu; Qiaofeng Yang; Xinghe Li; Hao Zhang; Zhisong Xiao; Mei Wang; Paul K. Chu; et al. (Chemical Engineering Journal, 2025)

Dynamic proteome and acetylome profiling reveals key regulators of sucrose accumulation in sugarcane - Miao Wang; Ao-Mei Li; Zhong-Liang Chen; Cui-Xian Qin; Fen Liao; You-Qiang Pan; Prakash Lakshmanan; Xiao-Feng Li; Dong-Liang Huang (Plant Cell Reports, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Fossil pods of tropical tree Peltophorum (Caesalpinioideae, Fabaceae) from southwestern China - Yi-Shan Zhao; Teng-Xiang Wang; Shu-Mei Xiao; Shu-Feng Li; Jian Huang (Review of Palaeobotany and Palynology, 2025)

A Gln alteration influences leaf morphogenesis by mediating gibberellin levels in tobacco - Qi-Li Mi; Hong-Tao Lv; Fei-Fei Huang; Li Xu; Zi-Ying Huang; Wen-Wu Yang; Mei-Yun Zou; Hai-Tao Huang; Wan-Li Zeng; Jia-Yin Zhao; Qing-Xian Chen; Yong-En Si-Tu; et al. (Journal of Plant Physiology, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Investigation into the kinetics, byproducts, and ecotoxicity of UV/NaClO-induced transformation of dibutyl phthalate in tap water - Mei Lan; Jialu Kong; Shanshan Li; Jifeng Yang; Haihui Luo; Yuanyuan Ying; Wenqing Huang (Journal of Water Process Engineering, 2025)

Migration of fungicides, antibiotics and resistome in the soil-lettuce system - Chenyu Huang; Minrong Cui; Tongxin Li; Conglai Zheng; Mengting Qiu; Mei Shan; Baotong Li; Luqing Zhang; Yunlong Yu; Hua Fang (Journal of Hazardous Materials, 2025)

Intelligent sensing platform based on europium-doped carbon dots for dual-functional detection of ciprofloxacin/Ga3+ and its tracking in vivo - Le Liang; Su-qian Cai; Yan-li Leng; Chan Huang; Yong-qing Liu; Ye Wang; Li Luo; Mei Han; Xiao-hong Li; Xiao-hua Cai (Journal of Hazardous Materials, 2025)

Collaborative performance of enzymatic saccharification and organic pollutant degradation from PHP (phosphoric acid coupled with hydrogen peroxide) pretreatment of lignocellulose - Miao Lei; Xuan Dong; Mei Huang; Li Zhao; Jianmei Zou; Dong Tian; Yongjia Lei; Jinsong He; Fei Shen (Journal of Environmental Management, 2025)

Algorithm for improving the sizing accuracy in real-time bioaerosol single particle mass spectrometer - Shaoyong Li; Lingjun Tang; Jingzhen Li; Zhanming Su; Zhengxu Huang; Mei Li; Wei Gao; Xue Li; Guohua Zhang; Lei Li (Journal of Aerosol Science, 2025)

Using isotope-tracer method with deuterium for quantitative study of hydrogen activation mechanism in direct coal liquefaction - Xiao-Dong Zhou; Xue-Long Yin; Lang Liu; Xue-Li Huang; Jing-Mei Liu; Ting Liu; He Lin; Feng-Yun Ma (Fuel, 2025)

Tree root-mediated soil metabolome in agroforestry enhancing the growth and quality of Panax notoginseng - Cuiying Wang; Guomin Mao; Yingbin Li; Wenjing Zi; Qingying Wang; Huichuan Huang; Min Yang; Fei Du; Xinyue Mei; Weiping Deng; Jian Lu; Shusheng Zhu; et al. (Plant and Soil, 2025)
Purpose The ecological cultivation of Panax notoginseng under a forest canopy relies on the coupling of the P. notoginseng growth environment and the forest ecosystem Methods In this study, six tree species, such as Platycladus orientalis (L.) Franco, were chosen to research the effects of species interactions on the growth, quality, and disease occurrence under intercropping with P. notoginseng , with single P. notoginseng serving as the control. Results Intercropping P. notoginseng with PO ( Platycladus orientalis , a coniferous tree species) or with SW ( Schima wallichii Choisy, a broad-leaved tree species) promoted the accumulation of P. notoginseng biomass, reduced the occurrence of root rot, improved the contents of nitrogen, phosphorus and potassium in P. notoginseng , and increased the saponin concentration. Then, 43 differentially abundant metabolites were screened in the P. notoginseng -tree intercropping system by soil metabolism analysis and compared with those in the monocropped system. Indole-3-carboxaldehyde showed a significant negative relationship with the occurrence of root rot disease and inhibited Fusarium oxysporum . In addition, 2-naphthalenesulfonic acid was significantly positively correlated with biomass and increased the dry weight in the underground part of P. notoginseng in the pot experiments. Conclusions Thus, the coniferous tree species PO and the broad-leaved tree species SW are potentially good neighbours of P. notoginseng , and soil metabolic changes may be important mechanisms for the growth and disease resistance benefits observed in the understorey of P. notoginseng .

Genetic patchiness of the endangered giant clam Tridacna maxima from Peninsular Malaysia - Li Keat Lee; Ya Yi Huang; Chaolun Allen Chen; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Po Teen Lim; Chui Pin Leaw (Coral Reefs, 2025)

A new isoflavone from the stems of Derris eriocarpa How - Ying Liu; Zhen-Xin Zhu; Yue Lu; Cong Wang; Hong-Cun Liu; Juan Meng; Jin Qi; Xiao-Ning Huang; Xiao-Mei Lu; Wen-Sen Lu; Shu-Han Luo; Hai-Na Liang; et al. (Natural Product Research, 2025)

Oral bacteriophage therapy effectively prevent and control of Clostridium perfringens type c infections in newborn piglets - Yuxing Wu; Lingyuan Zhang; Haodong Zheng; Weiqian Huang; Xiaochen Zhang; Wantong Ji; Runwen Ma; Xinyu Mao; Yonghua Huang; Xiaoxin Liu; Jialing Zeng; Shaowen Guo; et al. (Veterinary Microbiology, 2025)

Stability of China's terrestrial ecosystems carbon sink during 2000-2020 - Liang Shi; Honglin He; Li Zhang; Junbang Wang; Xiaoli Ren; Guirui Yu; Peng Hou; Jixi Gao; Bin Chen; Keyu Qin; Lili Feng; Shaoqiang Wang; et al. (Resources, Conservation and Recycling, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

Exposure to multiple metals and leukocyte telomere length in children and adolescents: The mediating effect of thyroid hormones - Qing Liu; Gaojie Fan; Jianing Bi; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Binghai Liu; Lianyan Yan; Wenwen Guo; Liqin Hu; Surong Mei; et al. (Environmental Research, 2025)

Onboard measurements of organic vapor emissions from river vessels under various operational conditions - Mengxue Tong; Yanli Zhang; Mei Li; Qi Wang; Xiao Tian; Dan Zhang; Aoqi Ge; Wei Song; Xin Xiong; Yinong You; Yongjang Xu; Yihua Huang; et al. (Environmental Pollution, 2025)

Reversible multilevel stimuli-responsiveness and multicolor room temperature phosphorescence to fluorescence transition based on a metal–organic framework system - Hui-Li Sun; Zhong-Hao Wang; Rui-Qi Huang; Zhuo-Di Chen; Mei Pan (Chemical Engineering Journal, 2025)

The complex interplay of flooding intensity and land use on soil microbial communities in riparian zones: Insights for ecological restoration - Kai Zhu; Fei Ye; Yu Mei; Weitao Jia; Xiai Zhu; Shuzhen Li; Shengjun Wu; Songlin Zhang; Ping Huang (CATENA, 2025)

Causes of Sphaeroma Outbreak in Mangroves of Dongzhai Harbor, China - Jiao Wen; Mei Li; Bo Huang; Jun Li (Wetlands, 2025)

Quantification of silica nanoparticle uptake at environmentally relevant concentrations by gold-core embedding - Mei Wang; Jia-Ming Li; Bin Huang; Ai-Jun Miao (Science of The Total Environment, 2024)

Prevalence of common upper gastrointestinal diseases in Chinese adults aged 18–64 years - Hong Yang; Mei Zhang; Hui Li; Zhengjing Huang; Yuanyuan Sun; Wenbo Li; Chun Li; Xuzhen Qin; Yanhong Wang; Xiao Zhang; Zhenping Zhao; Limin Wang; et al. (Science Bulletin, 2024)

A tumor-pH-responsive phthalocyanine as activatable type I photosensitizer for improved photodynamic immunotherapy - Ling Zhang; Rong-Bin Que; Ting-Ting Ke; Chao Wang; Wei Xie; Hong-Jie Sun; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang; Xingshu Li (Journal of Photochemistry and Photobiology B: Biology, 2024)

Recent advances in thermochemical conversion technology for anaerobic digestate from food waste - Changnan Mei; Mingqian Cheng; Ming Xie; Ruihao Yang; Tingting Liu; Zechun Huang; Tao Zhou; Youcai Zhao; Zewei Liu; Bin Li (Bioresource Technology, 2024)

Lactobacillus rhamnosus GG Regulates Host IFN-I Through the RIG-I Signalling Pathway to Inhibit Herpes Simplex Virus Type 2 Infection - Jingyu Wang; Mei Huang; Yuqi Du; Haoming Chen; Zixiong Li; Taiyu Zhai; Zihao Ou; Yiyi Huang; Fan Bu; Haojun Zhen; Ruoru Pan; Yubing Wang; et al. (Probiotics and Antimicrobial Proteins, 2024)
Numerous recent studies have demonstrated that the commensal microbiota plays an important role in host immunity against infections. During the infection process, viruses can exhibit substantial and close interactions with the commensal microbiota. However, the associated mechanism remains largely unknown. Therefore, in this study, we explored the specific mechanisms by which the commensal microbiota modulates host immunity against viral infections. We found that the expression levels of type I interferon (IFN-I) and antiviral priming were significantly downregulated following the depletion of the commensal microbiota due to treatment with broad-spectrum antibiotics (ABX). In addition, we confirmed a unique molecular mechanism underlying the induction of IFN-I mediated by the commensal microbiota. In vivo and in vitro experiments confirmed that Lactobacillus rhamnosus GG (LGG) can suppress herpes simplex virus type 2 (HSV-2) infection by inducing IFN-I expression via the retinoic acid-inducible gene-I (RIG-I) signalling pathway. Therefore, the commensal microbiota-induced production of IFN-I provides a potential therapeutic approach to combat viral infections. Altogether, understanding the complexity and the molecular aspects linking the commensal microbiota to health will help provide the basis for novel therapies already being developed. Graphical Abstract

Morpho-histological and Transcriptome Analysis Reveal the Unreduced Sperm Formation Mechanism in cdk1-Depletion Zebrafish - Yunbang Zhang; Rongyun Li; Hui Li; Yuwei Huang; Yihui Mei; Yuxuan Zheng; Yankun Guo; Zihao Zhou; Zhonglin Yong; Ying Zhao; Wenjing Dong; Jian Gao; et al. (Marine Biotechnology, 2024)

Sporelings and growth of the marine red alga, Gelidium elegans (Gelidiaceae), from Northern Taiwan - Showe-Mei Lin; Shih-Jhe Chen; Pin-Yu Huang; Li-Chia Liu; Yu-Shan Chiou (Journal of Applied Phycology, 2024)

Numerical investigation on effects of fuel rod with the position of bow deformation on the flow and heat transfer of PWR - Chengde Li; Mei Huang; Delong Sun; Xiaoping Ouyang; Yanping Huang; Yang Liu (Annals of Nuclear Energy, 2024)

Spatial classification model of port facilities and energy reserve prediction based on deep learning for port management―A case study of Ningbo - Huixiang Huang; Qiaoling Yan; Yang Yang; Yu Hu; Shaohua Wang; Qirui Yuan; Xiao Li; Qiang Mei (Ocean & Coastal Management, 2024)

Effect of wheat flour particle size on the quality deterioration of quick-frozen dumpling wrappers during freeze-thawed cycles - Lulu Yin; Xinyue Wu; Guolan Qin; Jiajing Han; Mei Liu; Yangkun Wei; Ying Liang; Jin Zhang; Shenying Zhang; Haojia Zhu; Ying Huang; Xueling Zheng; et al. (Food Research International, 2024)

Dual-mode SERS/colorimetric sensing of nitrite in meat products based on multifunctional au NPs@COF composite - Rui Tan; Mei Zeng; Qiuwen Huang; Na Zhou; Mengjiang Deng; Yuanyuan Li; Xiaojun Luo (Food Chemistry, 2024)

Temperature-driven divergence in molecular distribution and microbial invasion and the associated texture softening during dual-phase fermentation of Paocai - Lihong Ge; Yuli Huang; Xin Li; Ningxiaoxuan Wang; Jiaqi Liu; Mengting Liu; Yuan Mei; Menglu Yang; Jichun Zhao; Nan Zhao (Food Chemistry, 2024)

A novel antidepressant homogeneous polysaccharide YLP-1 from Millettia pulchra ameliorates tryptophan metabolism and SCFAs through modulating gut microbiota - Meng Yu; Cong-Cong Cai; Yun-Feng Huang; Yin-Di Zhu; Xin-Yao Luo; Xin-Yu Kong; Wen-Ting Zhang; Hui-Jun Li; Jing-Xian Fang; Zhong-Mei Zou (Carbohydrate Polymers, 2024)

Prenatal and childhood neonicotinoid exposure and neurodevelopment: A study in a young Taiwanese cohort - Pei-Wei Wang; Yu-Fang Huang; Li-Jung Fang; Mei-Lien Chen (Science of The Total Environment, 2024)

BrARR10 contributes to 6-BA-delayed leaf senescence in Chinese flowering cabbage by activating genes related to CTK, GA and ABA metabolism - Ci-mei Wang; Ze-xiang Zeng; Zong-li Liu; Jian-hua Zhu; Xin-guo Su; Ri-ming Huang; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Ying-ying Yang (Postharvest Biology and Technology, 2024)

Tailoring ethylenediamine functionalization on magnetic Zr-based metal-organic frameworks towards enhanced phosphate and tetracycline adsorption by synergy of Fe3O4 and amino functional groups - Yu Gao; A.-Wen Jiang; Shu-Hong Wang; Xiao-Mei Zhang; Kang-Qiang Lu; Kai Yang; Wei-Ya Huang; Dan Li (Journal of Environmental Chemical Engineering, 2024)

Synthesis of double Z-type heterojunction AgI/Ag6Si2O7/BiOI photocatalyst for antibiotics degradation and weakening toxicity - Zhaoxin Huang; Pengfei Zhu; Shasha Zhang; Ming Duan; Mei Liu; Xinglin Li (Journal of Environmental Chemical Engineering, 2024)

Revealing the intensification effect of circulating hydrothermal pretreatment: A sustainable route for biorefinery - Feiyue Shen; Chenjun He; Yuhang Wang; Jiayi Xu; Mei Huang; Li Zhao; Jinguang Hu; Dong Tian; Fei Shen (Chemical Engineering Journal, 2024)

Solvent-induced phase separation and Hofmeister effect enhanced strong, tough, and adhesive polyion complex hydrogels - Xuefeng Li; Xin Mei; Mengfan Chen; Dapeng Li; Qi Zeng; Jiayi Zhu; Shijun Long; Yiwan Huang (Chemical Engineering Journal, 2024)

Combined effects of nitrogen limitation and overexpression of malic enzyme gene on lipid accumulation in Dunaliella parva - Shi-Yu Liang; Li-Hua Li; Meng-Xiang Ling; Lei Mo; Li-Mei Huang; Ling-Ru Ruan; Chang-Hua Shang (Bioresource Technology, 2024)

In vitro cluster buds regeneration and control of shoot tip necrosis in tissue cultures of Trichosanthes cucumerina L. - Cheng-Li Liu; Jie-Mei Deng; Hong-Mei Yan; Heng-Yu Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Semi-synthesis and in vitro anti-cancer effects evaluation of novel xanthohumol derivatives - Xiaolong Sun; Jie Chen; Di Huang; Feng Ding; Long Zhao; Hong-Mei Li; Xiang-Shu Wang; Yu-Xin Zhang; Cheng-Zhu Wu (Molecular Diversity, 2024)

Effects of cadmium on the intestinal health of the snail Bradybaena ravida Benson - Yan-Mei Da; Shun-Shun Li; Yan-Qi Li; Le-Yu Deng; Ming-Jun Li; Tao Huang; Qing-Ye Sun; Jazbia Shirin; Guo-Wei Zhou (Ecotoxicology, 2024)

Effect of Foliar Application of Selenite On Organic Se and Antioxidant Activity in Kiwifruit - Yun-mei Lu; Mao Mu; Li-ai Wang; Ren-hua Huang (Applied Fruit Science, 2024)

Association of exposure to multiple metals with hemoglobin levels in Chinese children and adolescents - Fei Luo; Jianing Bi; Qing Liu; Gaojie Fan; Qing Fang; Xiya Qin; Xukuan Zhang; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; et al. (Science of The Total Environment, 2024)

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

Immunosuppressive alkaloids from Narcissus tazetta subsp. Chinensis and the mechanism of (+)-narciclasine in vitro and in vivo - Wen-Ling Wang; Xiu-Yin Wu; Xing-Yan Luo; Yu-Qin Tang; Jia Cui; Xin-Yue Huang; Yu-Chen Jiang; Yang Liu; Li-Mei Li (Phytochemistry, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Phthalocyanine J-aggregate nanoparticles with enormous-redshifted and intense absorption: Potential structure-J-aggregation relationships and application in tumor-associated macrophages-targeted phototheranostics - Fengxiang Tang; Haodong Yu; Yanzong Huang; Xue Zhao; Zixuan Chen; Honglin Ma; Bi-Yuan Zheng; Mei-Rong Ke; Yongfan Zhang; Xingshu Li; Juyoung Yoon; Jian-Dong Huang (Chemical Engineering Journal, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

A numerical method for two-dimensional transient nonlinear convection-diffusion equations - Xiangyuan Meng; Mei Huang; Boxue Wang; Xiaoping Ouyang; Yanping Huang; Denggao Chen; Yanting Cheng; Yaodi Li (Annals of Nuclear Energy, 2024)

Associations among global long interspersed nuclear element-1 DNA methylation, metal exposure, and chronic kidney disease - Yu-Mei Hsueh; Mei-Chieh Chen; Ying-Chin Lin; Chih-Yin Wu; Horng-Sheng Shiue; Sheng-Lun Hsu; Hsi-Hsien Chen; Ya-Li Huang (Archives of Toxicology, 2024)

Antibacterial and gut health effects of Amomum tsao‐ko in aquatic feed: A sustainable alternative to chemical antibiotics - Weiyao Peng; Guohui Liao; Lianzhang Wu; Jian Zhang; Juncai He; Penghui Gao; Yunsheng Cha; Shengjun You; Mei Huang; Jilan Zhou; Yuqiu He; Yi Yang; et al. (Journal of Fish Biology, 2024)
Amomum tsao‐ko Crevost et Lemarie (Zingiberaceae), an aromatic plant, has been considered to have diverse medicinal values and economic significance. It has been reported to possess antibacterial, antioxidant, and antidiabetic effects. With the increasing risk of diseases in aquaculture, there is a need for alternative solutions to chemical antibiotics. Plant extracts have shown promise as natural feed additives for aquatic animals. In this study, the antibacterial effect of Amomum tsao‐ko crude extracts was evaluated using the Oxford cup method. The extracts exhibited significant antimicrobial activity against Salmonella typhimurium and Salmonella enteritidis . Furthermore, the addition of Amomum tsao‐ko to fish feed resulted in notable changes in the gut structure of zebrafish and tilapia. The length and morphology of intestinal villi were enhanced, promoting improved digestion. Analysis of the gut microbial community revealed that Amomum tsao‐ko supplementation induced key changes in the gut microbial community composition of both zebrafish and tilapia. Notably, a 1% inclusion of Amomum tsao‐ko resulted in a marked rise in Proteobacteria levels in zebrafish, which diminished at 10% dosage. The supplement elicited mixed reactions among other bacterial phyla like Actinobacteria and Verrucomicrobiota. Fluctuations were also observed at the genus level, pointing to the concentration of Amomum tsao‐ko playing a pivotal role in influencing the structure of intestinal bacteria. The findings of this study suggest that Amomum tsao‐ko has antibacterial properties and can positively influence the gut health of fish. The potential use of Amomum tsao‐ko as a natural feed additive holds promise for improving aquaculture practices and reducing reliance on chemical antibiotics. Further research is needed to explore the full potential and applications of Amomum tsao‐ko in fish feed development.

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

Insecticide resistance and characteristics of mutations related to target site insensitivity of diamondback moths in Taiwan - Chia-Che Chang; Shu-Mei Dai; Chien-Yu Chen; Li-Hsin Huang; Yu-Hsien Chen; Ju-Chun Hsu (Pesticide Biochemistry and Physiology, 2024)

An empirical model for prediction of centimeter wave attenuation during haze event considering particle humidity and charge - Tian-Li Bo; Xiao-Hua Yang; Zhi-Mei Huang (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Mutually reinforced cancer treatment based on phototherapy combined with ferroptosis - Guan-Hong Chen; Lei Gan; Li-Yuan Tian; Bin-Xin Huang; Qiang Xiao; Yi-Jing Zhang; Mei-Tian Xiao; Bing-De Zheng; Jing Ye (Chemical Engineering Journal, 2024)

Cooperative management can mitigate trade-offs between livestock production and ecological functions to promote grassland sustainability - Shanshan Li; Jianxin Jiao; A. Allan Degen; Wenyin Wang; Tianyun Qi; Mei Huang; Shixiao Xu; Zhanhuan Shang (Agriculture, Ecosystems & Environment, 2024)

Norditerpenoid alkaloids from Aconitum refractum var. circinatum as autophagy inducers - Mei-Zhen Ye; Zhen-Ling Wan; Hong-Yu Ruan; Yu-Qi Yang; Ying Chen; Lin Chen; Shuai Huang; Xian-Li Zhou (Phytochemistry, 2024)

Screening of superior wheat lines under nitrogen regulation and factors affecting grain quality improvement under high yield - Chuan Zhong; Zhaowei Zhang; Mei Huang; Qing Li; Yingxin Zhong; Xiao Wang; Jian Cai; Tingbo Dai; Qin Zhou; Dong Jiang (Journal of Cereal Science, 2024)

Potential structure–function relationships of pectic polysaccharides from quinoa microgreens: Impact of various esterification degrees - Jie Li; Jing Feng; Xiao Luo; Mei-Mei Qu Mo; Wen-Bing Li; Jing-Wei Huang; Shengpeng Wang; Yi-Chen Hu; Liang Zou; Ding-Tao Wu (Food Research International, 2024)

Gastric Cancer Mesenchymal Stem Cells Trigger Endothelial Cell Functional Changes to Promote Cancer Progression - Linjing Cui; Ting Liu; Chao Huang; Fumeng Yang; Liqi Luo; Li Sun; Yuanyuan Zhao; Deqiang Wang; Mei Wang; Yong Ji; Wei Zhu (Stem Cell Reviews and Reports, 2024)

Single particle mass spectral signatures from on-road and non-road vehicle exhaust particles and their application in refined source apportionment using deep learning - Yongjiang Xu; Zaihua Wang; Chenglei Pei; Cheng Wu; Bo Huang; Chunlei Cheng; Zhen Zhou; Mei Li (Science of The Total Environment, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Efficient Low-Temperature catalytic depolymerization of LLDPE into valuable compounds using H-ZSM-5 catalysts and water - Mei Ren; Jun Li; Manhong Huang; Donghui Chen; Xuelian Chen; Qi An; Songmei Sun (Fuel, 2024)

Incorporating carbon quantum dots into phosphotungstic acid ionic liquid materials for enhanced catalytic oxidative desulfurization - Jun Xiong; Haoxue Huang; Mei Zhang; Pin Song; Hongping Li; Jun Di (Fuel, 2024)

Formula model established through field application of glass slides and rapid analysis of pesticide residues in vegetables by ion mobility spectrometry - Yong Mei; Mingfeng Huang; Wayne Jiang; Gaoqing Yuan; Xuesheng Li (Food Control, 2024)

Sugarcane borers: species, distribution, damage and management options - Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Yong Zhao; Cui-Xian Qin; Miao Wang; You-Qiang Pan; Shao-Long Wei; Dong-Liang Huang (Journal of Pest Science, 2024)
Lepidopteran borers stand out as the most destructive pests in sugarcane, leading to reductions in stalk weight, juice quality and sugar recovery. Presently, integrated pest management (IPM) systems are utilized for sugarcane borer management, employing diverse methods encompassing cropping system, chemical pesticides, behavioral manipulation, biological agents and the selection of resistant varieties. However, the effectiveness of this strategy remains controversial due to concerns about harmful residues, formulation limitations, environmental variability, labor shortages and increased input costs. Currently, multiple lines of transgenic sugarcane expressing insecticidal genes from the bacterium Bacillus thuringiensis (Bt) have been developed globally, offering the prospect of increases production with reduced pesticides application, thereby eliminating the negative effect of IPM. In Brazil, the first genetically modified sugarcane cultivars resistant to the sugarcane borer have been approved and released for commercial cultivation, shedding a bright light on a viable solution for sugarcane borers. This paper reviews borer species and distribution, the significant damage caused by sugarcane borers, current control approaches and the future effective control strategies. Additionally, this work provides comprehensive understanding on Bt sugarcane, serving as an additional tool to complement conventional sugarcane borers control resistance programs.

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Characterization of the complete mitochondrial genome of Ergasilus anchoratus Markevich, 1946 (Ergasilidae) and phylogeny of Copepoda - Cong-jie Hua; Yan Huang; Hui-quan Li; Jin-mei Feng; Jia-lu Qiao; Song Hu; Wei Liu; Xi-ji Shu (Systematic Parasitology, 2024)

Cell-excreted proteins mediate the interactions of differently sized silica nanoparticles during cellular uptake - Bin Huang; Jia-Ming Li; Xiao-Mei Zang; Mei Wang; Wei Pan; Ke-Da Zhang; Huan He; Qiao-Guo Tan; Ai-Jun Miao (Journal of Hazardous Materials, 2024)

Facet-dependent transformation and toxicity of nanoscale zinc oxide in the synthetic saliva - Xiang Zhang; Yunpeng Huang; Jikun Wang; Jie Tang; Yang Mei; Nali Zhu; Zhigang Li; Lingxiangyu Li; Yawei Wang (Journal of Environmental Sciences, 2024)

Bio-based adsorption foam composed of MOF and polyethyleneimine-modified cellulose for selective anionic dye removal - Zihui Yuan; Feng Li; Xuefeng Zhang; Mei-Chun Li; Yan Chen; Cornelis F. de Hoop; Jinqiu Qi; Xingyan Huang (Environmental Research, 2024)

An oxygen isotope perspective on the break-up of the Rodinia supercontinent - Hao Zou; Chang-Cheng Huang; Hua-Wen Cao; Chun-Mei Liu; Hui-Dong Yu; Franco Pirajno; Xian-Hua Li (Earth-Science Reviews, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

An Hsp70 promoter–based mouse for heat shock–induced gene modulation - Hangang Chen; Yangli Xie; Mei Zhang; Junlan Huang; Wanling Jiang; Ruobin Zhang; Can Li; Xiaolan Du; Hua Chen; Qiang Nie; Sen Liang; Qiaoyan Tan; et al. (Journal of Molecular Medicine, 2024)

Two new chromone derivatives from the rhizosphere soil fungus Ilyonectria robusta - Min Kuang; Wei-Wei Peng; Yuan-Tao Huang; Mei-Fang Li; Si-Yu Qin; Yu-Ting Zheng; Li Xu; Qi Huang; Zhen-Xing Zou (Natural Product Research, 2024)

Pseudocercones A-C, three new polyketide derivatives from the endophytic fungus Pseudocercospora sp. TSS-1 - Wei-Wei Peng; Min Kuang; Yuan-Tao Huang; Mei-Fang Li; Yu-Ting Zheng; Li Xu; Jian-Bing Tan; Feng-Hua Kang; Hai-Bo Tan; Zhen-Xing Zou (Natural Product Research, 2024)

Acetyl-11-keto-beta-boswellic acid inhibits cell proliferation and growth of oral squamous cell carcinoma via RAB7B-mediated autophagy - Dan Pan; Qing Wang; Shouyi Tang; Xingbo Wu; Luyao Cai; Zhen Wang; Ying Li; Mei Huang; Yu Zhou; Ying-Qiang Shen (Toxicology and Applied Pharmacology, 2024)

A prediction index of the volatile organic compounds pollution conditions in a chemical industrial park based on atmospheric stability - Xi Chen; Bo Huang; Mei Li; Runhui Xiao; Mingfu Cai; Zhihua Zhou; Song Ma; Wei Gao; Zhen Zhou (Science of The Total Environment, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Effect of vent area on vented ammonia-hydrogen-air deflagrations in a 1-m-long duct - Shikai Huang; Jin Guo; Liang Mei; Zexuan Yang; Hongyan Wang; Yiming Li (Fuel, 2024)

Knockdown of Notch Suppresses Epithelial-mesenchymal Transition and Induces Angiogenesis in Oral Submucous Fibrosis by Regulating TGF-β1 - Jinrong Wang; Liyan Yang; Jie Mei; Zhixin Li; Yuqi Huang; Honglan Sun; Kaiyue Zheng; Huifang Kuang; Wen Luo (Biochemical Genetics, 2024)

Modulation of plasmacytoid dendritic cell and CD4+ T cell differentiation accompanied by upregulation of the cholinergic anti-inflammatory pathway induced by enterovirus 71 - Li Li; Rong-Wei Huang; Xiao-Ning Liu; Xiao-Yi Xiang; Yuan-Tao Zhou; Xing-Xing Feng; Lv-Yuan Tao; Jia Yu; Qin Yi; Yan-Chun Wang; Xiao-Mei Liu (Archives of Virology, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

How does adsorptive fractionation of dissolved black carbon on ferrihydrite affect its copper binding behaviors? A molecular-scale investigation - Mei Huang; Qi Yang; Jianmei Zou; Li Zhao; Jinsong He; Dong Tian; Yongjia Lei; Fei Shen (Water Research, 2024)

Land intensification use scenarios based on urban land suitability assessment of the national park - Tianyun Qi; Yu Li; Mei Huang; Binyu Luo; Zhen Peng; Wenyin Wang; Shanshan Li; A. Allan Degen; Zhanhuan Shang (Sustainable Cities and Society, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Highly efficient adsorption of ciprofloxacin from aqueous solutions by waste cation exchange resin-based activated carbons: Performance, mechanism, and theoretical calculation - Qiang Li; Haochen Li; Xiaofei Zong; Haochao Sun; Yunhao Liu; Ziyi Zhan; Shou Mei; Yanjie Qi; Yangbo Huang; Yuxuan Ye; Fei Pan (Science of The Total Environment, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

Unveiling the inhibition of chlortetracycline photodegradation and the increase of toxicity when coexisting with silver nanoparticles - Yajun Tian; Chuhan Ying; Liqiu Zhang; Huimin Huang; Shuang Song; Rongwu Mei; Jun Li (Science of The Total Environment, 2024)

An integrated study of constraining the initial 230Th of a stalagmite and its implications - Shouyi Huang; Yanjun Cai; Hai Cheng; Gang Xue; Xing Cheng; Mei He; Ruoxin Li; Le Ma; Yingying Wei; Yanbin Lu; Ling Yang; R. Lawrence Edwards (Quaternary Geochronology, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Homoerythrina-type alkaloids with neuroprotective activity from the branches of Cephalotaxus hainanensis Li - Hao Yan; Hao Wang; Peng-Wei Chen; Li Yang; Hui-Qin Chen; Fei Wu; Pei Wang; Hao-Fu Dai; Xiao-Long Huang; Shuang-Qing Zhou; Wen-Li Mei (Phytochemistry Letters, 2024)

The role of abiotic and biotic factors of aged brine in directing microbial assembly and volatile profiles of Paocai during fermentation - Nan Zhao; Yuli Huang; Haimei Lai; Yali Wang; Yuan Mei; Xueqing Zeng; Menglu Yang; Jichun Zhao; Huajia Li; Yongqing Zhu; Renyou Gan; Lihong Ge (Food Bioscience, 2024)

Effects of arbuscular mycorrhizal fungi on uptake, partitioning and use efficiency of nitrogen in wheat - Jiawen Xue; Lili Guo; Liulong Li; Zhaowei Zhang; Mei Huang; Jian Cai; Xiao Wang; Yingxin Zhong; Tingbo Dai; Dong Jiang; Qin Zhou (Field Crops Research, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Scalable, bio-inspired and self-floating bi-layer polyurethane foam solar evaporator with excellent capillary hydrodynamic effect - Jing Lin; Mei Wu; Hao Fang; Mengyue Wu; Shikuo Li; Hui Zhang; Yu Jiang; Fangzhi Huang (Chemical Engineering Journal, 2024)

Unravelling structure sensitivity in heterogeneous hydroformylation of aldehyde over Rh - Qi Yang; Pengfei Wang; Chen Li; Benlei Wang; Ying Zheng; Yi Feng; Zidi Miao; Maoshuai Li; Mei-Yan Wang; Shouying Huang; Xinbin Ma (Chemical Engineering Journal, 2024)

Circulating Lipoproteins Mediate the Association Between Cardiovascular Risk Factors and Cognitive Decline: A Community-Based Cohort Study - Jialin Li; Qingxia Huang; Yingzhe Wang; Mei Cui; Kelin Xu; Chen Suo; Zhenqiu Liu; Yanpeng An; Li Jin; Huiru Tang; Xingdong Chen; Yanfeng Jiang (Phenomics, 2024)

Oncogenic and immunological roles of RACGAP1 in pan-cancer and its potential value in nasopharyngeal carcinoma - Cheng-shan Zheng; Wei-mei Huang; Hong-mei Xia; Jing-lin Mi; Yuan-qing Li; Hui-qing Liang; Li Zhou; Zhou-xue Lu; Fang Wu (Apoptosis, 2024)

How the intrinsic functional connectivity patterns of the semantic network support semantic processing - Chengmei Huang; Aqian Li; Yingdan Pang; Jiayi Yang; Jingxian Zhang; Xiaoyan Wu; Leilei Mei (Brain Imaging and Behavior, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

The swelling induced choline alkali-urea (SICAU) process for sustainable crop straw upgrading - Yuehan Jiang; Feiyue Shen; Baiheng Jiang; Yuheng Hu; Jinguang Hu; Mei Huang; Li Zhao; Hejun Wu; Dong Tian; Fei Shen (Chemical Engineering Journal, 2024)

Extraction of super high-yield lignin-carbohydrate complexes from rice straw without compromising cellulose hydrolysis - Baiheng Jiang; Feiyue Shen; Yuehan Jiang; Mei Huang; Li Zhao; Yongjia Lei; Jinguang Hu; Dong Tian; Fei Shen (Carbohydrate Polymers, 2024)

Hydrothermal apatite as a robust U–Th–Pb chronometer for the Carlin-type gold deposits in the Youjiang basin, SW China - Wei Gao; Ruizhong Hu; Yong Huang; Jingjing Zhu; Qiuli Li; Lu Mei; Xianwu Bi; Jianzhong Liu (Mineralium Deposita, 2024)

Miniaturized ascorbic acid assay platform based on point discharge atomic emission spectrometry coupling with gold filament enrichment - Yanping Wang; Yuemei Chen; Kejun Li; Jinrong Zhou; Xin Yuan; Mei Zhang; Ke Huang (Analytica Chimica Acta, 2024)

Electrochemical detoxification of tetrabromobisphenol A-contaminated water using Ti/SnO2-Sb/PbO2-Ce anodic membrane - Jiaqi Wei; Yuanyuan Zhang; Jinxing Ma; Shanshan Wang; Minmin Jiang; Qiaoyan Wei; Mei Chen; Xiaowu Huang; Haixiang Li; Xuehong Zhang; Junjian Zheng (Journal of Water Process Engineering, 2023)

Illumination and reconstruction of keystone microbiota for reproduction of key flavor-active volatile compounds during paocai (a traditional fermented vegetable) fermentation - Nan Zhao; Yuli Huang; Haimei Lai; Yali Wang; Yuan Mei; Xueqing Zeng; Menglu Yang; Huajia Li; Jichun Zhao; Yongqing Zhu; Yong Zuo; Lihong Ge (Food Bioscience, 2023)

A co-twin control study of in utero exposure to poly- and perfluoroalkyl substances and associations with neonatal thyroid-stimulating hormone - Liqin Hu; Hong Mei; Xiaonan Cai; Feiyan Xiang; Na Li; Zhen Huang; Zhengrong Duan; Pan Yang; Han Xiao (Environmental Research, 2023)

Enhancing battery module safety with insulation material: Hollow glass microspheres incorporating aerogel of varying particle sizes - Yin Yu; Zhiyuan Li; Zesen Wei; Shiyao Chen; Zonghou Huang; Zheng Fang; Yuxuan Li; Junjie Wang; Wenxin Mei; Qingsong Wang (Chemical Engineering Journal, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Influence of interaction among multiple cracks on crack propagation in nozzle corner of reactor pressure vessel - YanTing Cheng; Mei Huang; YaoDi Li; WeiYang Liu; BoXue Wang; XiangYuan Meng; XiaoPing Ouyang (Annals of Nuclear Energy, 2023)

Three new triterpenoid glycosides from Aronia melanocarpa (Michx.) Elliott - Ting-Ting Guo; Man-Li Zhang; Zhao-Cui Sun; Li-Mei Zhang; Xu-Dong Xu; Bi-Huang Hu (Natural Product Research, 2023)

The microbial mechanisms by which long-term heavy metal contamination affects soil organic carbon levels - Zhineng Xiao; Changqun Duan; Shiyu Li; Ji Chen; Changhui Peng; Rongxiao Che; Chang'e Liu; Yin Huang; Runran Mei; Liangliang Xu; Pengfei Luo; Yadong Yu (Chemosphere, 2023)

Amino-terminated carbon dots for imaging Golgi apparatus polarity in live cells - Lei Zhan; Peng Hou; Na Chen; Yuan Fang Li; Chun Mei Li; Cheng Zhi Huang (Chemical Engineering Journal, 2023)

Dextran-based micelles for combinational chemo-photodynamic therapy of tumors via in vivo chemiluminescence - Chendi Ding; Zhaoqing Shi; Meitong Ou; Yingbang Li; Li Huang; Wenyan Wang; Qili Huang; Meihang Li; Chunbo Chen; Xiaowei Zeng; Hongzhong Chen; Lin Mei (Carbohydrate Polymers, 2023)

Thermal-hydraulic CFD simulation of PWR 5 × 5 bowing fuel assembly - Boxue Wang; Mei Huang; Weiyang Liu; Yaodi Li; Yanting Cheng (Annals of Nuclear Energy, 2023)

Synergistic impact of co-exposures to whole blood metals on chronic kidney disease in general US adults: a cross‑sectional study of the National Health and Nutrition Examination Survey 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Wen-wen Bao; Yu-shan Zhang; Li-xin Hu; Shan Huang; Nan Jiang; Shao-yi Huang; Xue-ya Pu; Guang-hui Dong; Ya-jun Chen (Environmental Science and Pollution Research, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

On conflict of natural resources-carbon emissions nexus in China: The role of economic policy uncertainty - Maoran Ye; Ling Tang; Lin Huang; Mei Li (Resources Policy, 2023)

Preharvest glycerol treatment enhances postharvest storability of orange fruit by affecting cuticle metabolism - Zhifeng Zhu; Wanjun Mei; Ruixue Li; Huan Liu; Shuying Chen; Hongbin Yang; Rangwei Xu; Taojiang Huang; Jingsong Xiang; Feng Zhu; Yunjiang Cheng (Postharvest Biology and Technology, 2023)

CaHMA1 promotes Cd accumulation in pepper fruit - Weihong Xu; He Huang; Xiaodong Li; Mei Yang; Sunlin Chi; Yu Pan; Nannan Li; Andrew H. Paterson; Yourong Chai; Kun Lu (Journal of Hazardous Materials, 2023)

Exposure to per- and polyfluoroalkyl substances in women with twin pregnancies: Patterns and variability, transplacental transfer, and predictors - Songyi Huang; Xiaojie Li; Langjing Deng; Jinying Xie; Guangtong Huang; Chenyan Zeng; Nanxin Wu; Sui Zhu; Chaoqun Liu; Hong Mei; Han Xiao; Da Chen; et al. (Journal of Hazardous Materials, 2023)

The coupling effects between acid-catalyzed hydrothermal pretreatment and acidic/alkaline deep eutectic solvent extraction for wheat straw fractionation - Na Pan; Baiheng Jiang; Jinguang Hu; Mei Huang; Jinsong He; Qin Jiang; Li Zhao; Fei Shen; Dong Tian (Bioresource Technology, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Rational design of genotyping nanodevice for HPV subtype distinction - De Yu Li; Yong Jian Jiang; Kun Han Nie; Jing Li; Yuan Fang Li; Cheng Zhi Huang; Chun Mei Li (Analytica Chimica Acta, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

A fluorescent lateral flow immunoassay based on CdSe/CdS/ZnS quantum dots for sensitive detection of olaquindox in feedstuff - Mei Hu; Xiaofei Hu; Guoqiang Wang; Yongxia Cheng; Xiaoling Yu; Xianqing Huang; Yu Li (Food Chemistry, 2023)

Low-dose benzo[a]pyrene exposure induces hepatic lipid deposition through LCMT1/PP2Ac-mediated autophagy inhibition - Yunqing Li; NingJing Liang; Tingting Tang; Zhijian Zheng; Muting Chen; Jiao Mo; Ning Zhang; Simi Liao; Yu Lei; Yijie Wu; Chunhua Lan; Huan Ding; et al. (Food and Chemical Toxicology, 2023)

Nitrogen addition stimulated soil respiration more so than carbon addition in alpine meadows - Mei Huang; Xiaopeng Chen; A. Allan Degen; Ruiying Guo; Tao Zhang; Binyu Luo; Haiyan Li; Jingxue Zhao; Zhanhuan Shang (Environmental Research, 2023)

Evaluation of the impacts of ozone on the vegetation productivity of woodland and grassland ecosystems in China - WANG Qinyi; HUANG Mei; WANG Shaoqiang; CHEN Bin; LIU Zhenhai; WANG Zhaosheng; CHEN Shiliang; LI Hui; ZHU Tongtong; LI Donghui; LI Yuelin; Lin Hu; et al. (Ecological Modelling, 2023)

Cascade utilization of crop straw through a FeCl3-mediated deep eutectic solvent biorefinery: Lignin-containing cellulose nanofibers flocculant fabrication followed by fertilizer production - Yiyi Chen; Chaojie Yang; Jinguang Hu; Mei Huang; Li Zhao; Jinsong He; Shaobo Zhang; Fei Shen; Dong Tian (Chemical Engineering Journal, 2023)

Joint effect of whole blood metals exposure with dyslipidemia in representative US adults in NHANES 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Li-xin Hu; Wen-wen Bao; Yu-shan Zhang; Aerziguli Kakaer; Yu Zhao; Yi-can Chen; Xue-ya Pu; Shao-yi Huang; Nan Jiang; et al. (Environmental Science and Pollution Research, 2023)

Heterogeneous Fenton water purification catalyzed by iron phosphide (FeP) - Shu-Chuan Mei; Liang Li; Gui-Xiang Huang; Xiao-Qiang Pan; Han-Qing Yu (Water Research, 2023)

Cooperation mode for concrete formwork reuse among construction sites - Zhongya Mei; Maozeng Xu; Heng Li; Zhongyi Huang; Siyu Luo (Sustainable Cities and Society, 2023)

Controlled deposition via a bifunctional layer enables dendrite-free zinc metal batteries - Han Wang; Quanyu Li; Shaozhen Huang; Liangjun Zhou; Lin Mei; Zhibin Wu; Baihua Qu; Weifeng Wei; Xiaobo Ji; Yuejiao Chen; Libao Chen (Chemical Engineering Journal, 2023)

Static magnetic field increases aerobic nitrogen removal from hypersaline wastewater in activated sludge with coexistence of fungi and bacteria - Jun Chen; You-Wei Cui; Mei-Qi Huang; Hui-Juan Yan; Dong Li (Bioresource Technology, 2023)

Increased risk of respiratory and allergic diseases in preschoolers from building envelope dampness exposure: Repeated cross-sectional surveys in multicity China - Wei Yu; Yan Zhang; Baizhan Li; Yinping Zhang; Chenqiu Du; Zhuohui Zhao; Dan Norback; Jiao Cai; Qihong Deng; Chan Lu; Hua Qian; Xiaohong Zheng; et al. (Building and Environment, 2023)

A comprehensive approach to quantify the source identification and human health risk assessment of toxic elements in park dust - Chang-Chen Huang; Li-Mei Cai; Yao-Hui Xu; Luo Jie; Guo-Cheng Hu; Lai-Guo Chen; Han-Zhi Wang; Xu-Bang Xu; Jing-Xian Mei (Environmental Geochemistry and Health, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

Four new terpenoids and other metabolites with potential anti-complementary activities from the aerial parts of Dracocephalum moldavica (Lamiaceae) - Jiaming Wang; Jinfeng Sun; Long Jin; Yanyan Huang; Mengjie Wang; Mei Jin; Shengbao Diao; Wei Zhou; Gao Li (Natural Product Research, 2023)

Binding of Cd(II) to birnessite and fulvic acid organo-mineral composites and controls on Cd(II) availability - Changsheng Jin; Zhongwu Li; Mei Huang; Xiang Ding; Mi Zhou; Jia Chen; Bolin Li (Chemosphere, 2023)

Chemical characterization and source attribution of organic pollutants in industrial wastewaters from a Chinese chemical industrial park - Yihua Huang; Yinong You; Manman Wu; Min Han; Jin Zhang; Wei Gao; Danping Xie; Hongzhan Chen; Hui Ou; Ninghui Song; Chunlei Cheng; Wen Zhuang; et al. (Environmental Research, 2023)

Fully upgrade lignocellulose to three nanomaterials by combinational pretreatment: Refining straw waste to pesticide nanocarrier - Feiyue Shen; Chenjun He; Yuhang Wang; Jinguang Hu; Mei Huang; Li Zhao; Shaobo Zhang; Dong Tian; Fei Shen (Chemical Engineering Journal, 2023)

Evaluation of the treatment effect of rear slope cutting on hydrodynamic pressure landslides: A case study - Li Wang; Jun-jie Huang; Yong Chen; Shi-mei Wang; Zhi-hong Fan; Fei Guo; Xiao-wei Li (Journal of Mountain Science, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Metal ions-regulated chemical vapor generation of Hg2+:mechanism and application in miniaturized point discharge atomic emission spectrometry assay of oxalate in clinical urolithiasis samples - Haiyan Yang; Liping Qi; Jinrong Zhou; Qian Li; Xin Yuan; Mei Zhang; Yong He; Ke Huang; Piaopiao Chen (Analytica Chimica Acta, 2023)

Environmental conditions affecting the germination of Puccinia hemerocallidis urediniospores - Qiaoping Qin; Dongmei Huang; Mei Li; Min Fan (Journal of Plant Pathology, 2023)

Antibiofilm mechanism of dielectric barrier discharge cold plasma against Pichia manshurica - Xinlei Hou; Jin Wang; Yuan Mei; Lihong Ge; Jing Qian; Yuli Huang; Menglu Yang; Huajia Li; Yanli Wang; Zhengcai Yan; Dengshui Peng; Jianhao Zhang; et al. (Innovative Food Science & Emerging Technologies, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

The effect of phthalates exposure during pregnancy on asthma in infants aged 0 to 36 months: a birth cohort study - Jian-Qing Wang; Chun-Mei Liang; Ya-Bin Hu; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Peng Zhu; Jia-Hu Hao; Fang-Biao Tao (Environmental Geochemistry and Health, 2023)

Effects of grazing exclusion on vegetation community characteristics over 22 years in the Zoige alpine meadows from China - Xue Jiang; Li He; Yanping Qu; Banghong Jian; Dongzhou Deng; Mei Liu; Jingtian Yang; Yunlong Ma; Dechao Chen; Yi Huang (Acta Oecologica, 2023)

A pair of new oxindole alkaloids isolated from Uncaria macrophylla - Xin-Xin Liang; Jin-Xuan Yang; Jian-Mei Li; Jia-Bi Huang; Liu-Meng Yang; Tian-Tian Sun; Rong-Hua Luo; Wei-Lie Xiao; Yong-Tang Zheng; Xiao-Li Li (Natural Product Research, 2023)

Emission factors and source profiles of volatile organic compounds from typical industrial sources in Guangzhou, China - Chunyan Jiang; Chenglei Pei; Chunlei Cheng; Huizhong Shen; Qianhua Zhang; Xiufeng Lian; Xin Xiong; Wei Gao; Ming Liu; Zixin Wang; Bo Huang; Mei Tang; et al. (Science of The Total Environment, 2023)

High bioethanol titer and yield from phosphoric acid plus hydrogen peroxide pretreated paper mulberry wood through optimization of simultaneous saccharification and fermentation - Pleasure Chisom Ajayo; Qing Wang; Mei Huang; Li Zhao; Dong Tian; Jinsong He; Dexin Fang; Jinguang Hu; Fei Shen (Bioresource Technology, 2023)

Chemical constituents from the aerial parts of Sambucus adnata Wall. and their chemotaxonomic significance - Zheng-Bo Wu; Mei-Mei Zheng; Shu-Ran Qin; Jiang-Li Huang; Dashan Li; Wen-Jing Wang (Biochemical Systematics and Ecology, 2023)

Identification of a suppressor for the wheat stripe rust resistance gene Yr81 in Chinese wheat landrace Dahongpao - Huiling Jin; Haipeng Zhang; Xuyang Zhao; Li Long; Fangnian Guan; Yunpeng Wang; Linyu Huang; Xiaoyue Zhang; Yuqi Wang; Hao Li; Wei Li; Zhien Pu; et al. (Theoretical and Applied Genetics, 2023)

Isothermal exponential amplification reactions triggered by circular templates (cEXPAR) targeting miRNA - Xue-mei Qu; Xiao-dong Ren; Ning Su; Xian-ge Sun; Shao-li Deng; Wei-ping Lu; Qing Huang (Molecular Biology Reports, 2023)

Hydrological properties of biochar-amended expansive soil under dynamic water environment and biochar-amended soil’s application in green roofs - Muyang Li; Ankit Garg; Shan Huang; Mingjie Jiang; Guoxiong Mei; Jiaqin Liu; Hao Wang (Acta Geophysica, 2023)

Quality assessment of variable collagen tissues of sea cucumber (Stichopus japonicus) body wall under different heat treatment durations by label-Free proteomics analysis - Yi-Zhen Huang; Yi-Sha Xie; Yan-Xin Li; Mei-Yu Zhao; Na Sun; Hang Qi; Xiu-Ping Dong (Food Research International, 2023)

Targeting high nutrient efficiency to reduce fertilizer input in wheat production of China - Saibin Hou; Haiyan Dang; Tingmiao Huang; Qiannan Huang; Chao Li; Xiaohan Li; Yingying Sun; Hongxin Chu; Weihong Qiu; Jinshan Liu; Mei Shi; Gang He; et al. (Field Crops Research, 2023)

P2X7Rs: new therapeutic targets for osteoporosis - Haoyun Huang; Yu-Mei He; Miao-Miao Lin; Yanchao Wang; Xiaomei Zhang; Li Liang; Xueling He (Purinergic Signalling, 2023)
Increasing evidence suggests that both the occurrence and progression of osteoporosis are associated with inflammation, especially in primary osteoporosis. The maintenance of skeletal homeostasis is dependent on the complex regulation of bone metabolism. Numerous evidence suggested that purinoceptor networks are essential for bone homeostasis. In this review, the relationship between inflammation and the development of osteoporosis and the role of P2X7 receptor (P2X7R) in regulating the dynamic regulation of bone reconstruction were covered. We also discussed how P2X7R regulates the balance between resorption and bone formation by osteoblasts and reviewed the relevance of P2X7R polymorphisms in skeletal physiology. Finally, we analyzed potential targets of P2X7R for osteoporosis.

Recent trends in degradation strategies of PFOA/PFOS substitutes - Zizi Li; Zhi-Mei Luo; Yanjun Huang; Jia-Wei Wang; Gangfeng Ouyang (Chemosphere, 2023)

Cross-scale sensing of field-level crop residue cover: Integrating field photos, airborne hyperspectral imaging, and satellite data - Sheng Wang; Kaiyu Guan; Chenhui Zhang; Qu Zhou; Sibo Wang; Xiaocui Wu; Chongya Jiang; Bin Peng; Weiye Mei; Kaiyuan Li; Ziyi Li; Yi Yang; et al. (Remote Sensing of Environment, 2023)

Detection of polycyclic aromatic hydrocarbons using a high performance-single particle aerosol mass spectrometer - Yao Zhang; Chenglei Pei; Jinwen Zhang; Chunlei Cheng; Xiufeng Lian; Mubai Chen; Bo Huang; Zhong Fu; Zhen Zhou; Mei Li (Journal of Environmental Sciences, 2023)

Mechanochemically activated microscale zero-valent iron with carboxymethylcellulose for efficient sequestration of phosphate in aqueous solution - Wenjuan Shen; Zhan Liu; Fengjiao Quan; Xu Zhang; Xing Peng; Xiaobing Wang; Wenqing Wang; Lan Huang; Shunxi Zhang; Jianfen Li; Yunjun Mei (Journal of Environmental Chemical Engineering, 2023)

Estimating the CO2 emissions of Chinese cities from 2011 to 2020 based on SPNN-GNNWR - Lizhi Miao; Sheng Tang; Xinting Li; Dingyu Yu; Yamei Deng; Tian Hang; Haozhou Yang; Yunxuan Liang; Mei-Po Kwan; Lei Huang (Environmental Research, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Thermal hydraulic analysis of a deformed SFR fuel assembly using CFD - YaoDi Li; Mei Huang; YanTing Cheng; Boxue Wang; Xiangyuan Meng (Annals of Nuclear Energy, 2023)

A new monoterpenoid glycoside and a new phenolic glycoside isolated from Dracocephalum moldavica and their anti-complementary activity - Jiaming Wang; Jinfeng Sun; Long Jin; Mengjie Wang; Yanyan Huang; Mei Jin; Wei Zhou; Gao Li (Natural Product Research, 2023)

Co-exposure to phenols and phthalates during pregnancy with the difference of body size in twins at one month old - Hong Mei; Langjing Deng; Jinying Xie; Xiaojie Li; Nanxin Wu; Liqin Hu; Guangtong Huang; Fanyu Mo; Da Chen; Han Xiao; Pan Yang (Chemosphere, 2023)

Comparative transcriptome analysis of early sexual differentiation in the male and female gonads of common carp (Cyprinus carpio) - Mei Wang; Lin Chen; Zhixiong Zhou; Junzhu Xiao; Baohua Chen; Peihong Huang; Chengyu Li; Yaguo Xue; Ruoting Liu; Yulin Bai; Mengzhen Yan; Shuimu Hu; et al. (Aquaculture, 2023)

A new water-soluble lignin incorporation enhanced the barrier performance of liquid mulching film - Dong Tian; Jing Zhang; Jinguang Hu; Mei Huang; Li Zhao; Yongjia Lei; Jianmei Zou; Shaobo Zhang; Fei Shen (Chemical Engineering Journal, 2023)

Bioinspired, stable adhesive Ti3C2Tx MXene-based coatings towards fire warning, smoke suppression and VOCs removal smart wood - Yin Zhang; Yanping Huang; Mei-Chun Li; Shuai Zhang; Weimin Zhou; Changtong Mei; Mingzhu Pan (Chemical Engineering Journal, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Spatiotemporal variations of water use efficiency and its driving factors in Inner Mongolia from 2001 to 2020 - Li Mei; Siqin Tong; Shan Yin; Yuhai Bao; Xiaojun Huang; Tuya Alateng; Yongfang Wang; Enliang Guo; Zhihui Yuan; Dalai Nashun; Suriguga Gao; Xinyi Liu; et al. (Journal of Geographical Sciences, 2023)

Three-fluorescence sensor for minute-time scale low-cost analysis of urinary oxalate in urolithiasis metabolic assessment - Xin Jiang; Yunjin Bai; Qilin Liu; Li Yan; Tingting Long; Mei Li; Jin Huang; Binwu Ying; Piaopiao Chen (Analytica Chimica Acta, 2023)

Scaling-up and proteomic analysis reveals photosynthetic and metabolic insights toward prolonged H2 photoproduction in Chlamydomonas hpm91 mutant lacking proton gradient regulation 5 (PGR5) - Peng Liu; De-Min Ye; Mei Chen; Jin Zhang; Xia-He Huang; Li-Li Shen; Ke-Ke Xia; Xiao-Jing Xu; Yong-Chao Xu; Ya-Long Guo; Ying-Chun Wang; Fang Huang (Photosynthesis Research, 2022)
Clean and sustainable H 2 production is crucial to a carbon–neutral world. H 2 generation by Chlamydomonas reinhardtii is an attractive approach for solar-H 2 from H 2 O. However, it is currently not large-scalable because of lacking desirable strains with both optimal H 2 productivity and sufficient knowledge of underlying molecular mechanism. We hereby carried out extensive and in-depth investigations of H 2 photoproduction of hpm91 mutant lacking PGR5 (Proton Gradient Regulation 5) toward its up-scaling and fundamental mechanism issues. We show that hpm91 is at least 100-fold scalable (up to 10 L) with continuous H 2 collection of 7287 ml H 2 /10L-HPBR in averagely 26 days under sulfur deprivation. Also, we show that hpm91 is robust and active during sustained H 2 photoproduction, most likely due to decreased intracellular ROS relative to wild type. Moreover, we obtained quantitative proteomic profiles of wild type and hpm91 at four representing time points of H 2 evolution, leading to 2229 and 1350 differentially expressed proteins, respectively. Compared to wild type, major proteome alterations of hpm91 include not only core subunits of photosystems and those related to anti-oxidative responses but also essential proteins in photosynthetic antenna, C/N metabolic balance, and sulfur assimilation toward both cysteine biosynthesis and sulfation of metabolites during sulfur-deprived H 2 production. These results reveal not only new insights of cellular and molecular basis of enhanced H 2 production in hpm91 but also provide additional candidate gene targets and modules for further genetic modifications and/or in artificial photosynthesis mimics toward basic and applied research aiming at advancing solar-H 2 technology.

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Comparison of infections with respiratory syncytial virus between children and adults: a multicenter surveillance from 2015 to 2019 in Beijing, China - Ming Luo; Cheng Gong; Yan Zhang; Xue Wang; Yang Liu; Qing Luo; Maozhong Li; Aihua Li; Yiting Wang; Mei Dong; Wenbo Xu; Fang Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Characteristic pollutants risk assessment of modified manganese residue utilization in sintered product - Chao-qiang Wang; Ke Liu; De-ming Huang; Qi-cong Huang; Pei-xin Wang; Xu-dong Mei; Shu-chun Li (Environmental Science and Pollution Research, 2022)

Ecological consequences of China’s regional development strategy: evidence from water ecological footprint in Yangtze River Economic Belt - Changsheng Jin; Yuxi Liu; Zhongwu Li; Rizhao Gong; Mei Huang; Jiajun Wen (Environment, Development and Sustainability, 2022)

Solute Carrier Family 27 Member 6 (SLC27A6) Possibly Promotes the Proliferation of Papillary Thyroid Cancer by Regulating c-MYC - Changjian Liu; Jian Wang; Dongdong Li; Ruoxuan Ni; Mei Zhao; ChangZhi Huang; Shaoyan Liu (Biochemical Genetics, 2022)

Growth Performance, Nutritional Quality, and Immune-Related Gene Expression of the Chinese Mitten Crab (Eriocheir sinensis) in Pond Ecosystem as Influenced by Stocking Density - Ziyu Wang; Zhenfang Mao; Xiaoyong Li; Minjie Zhu; Linjie Li; Feng Mei; Peiying Huang; Jiahao Hou; Shaoqin Jian; Daxian Zhao (Fishes, 2022)
This study aimed to evaluate the influence of stocking density on growth performance, nutritional quality, and immune-related gene expression of Eriocheir sinensis and water quality in pond ecosystems. E. sinensis were randomly divided into five density groups (G1: 1.2 inds/m2; G2: 1.5 inds/m2; G3: 1.8 inds/m2; G4: 2.1 inds/m2; G5: 2.4 inds/m2) based on their breeding densities, and three replicates were set up for each density group, for a total of fifteen ponds. After 169 days of breeding, the muscle, hepatopancreatic tissue, and hemolymph of E. sinensis, randomly selected from each group, were collected for analysis. Body weight (BW), carapace length, and carapace width increased with breeding time, and the BW of E. sinensis in G3 was higher than that in the other groups. In the muscle and hepatopancreas, the crude lipid content in the G3 group was higher than that in the other groups (p > 0.05). In the muscle tissue, the contents of total, essential, and delicious amino acids in the G3 group were higher than those in the other groups. The expression levels of immune-related genes in G5 were higher than those in the other groups. The value of pH decreased and NO2-N increased significantly in the G5 group and pH, as a synergetic factor of culture density, affected the growth performance of E. sinensis. In conclusion, stocking density has a certain impact on the growth performance, nutrition quality, and immunity of E. sinensis and water quality in pond ecosystems, and a stocking density of 1.8 inds/m2 can be considered optimal for rearing in pond ecosystems of the Poyang Lake region.

Synthesis and biological evaluation of (+)-paeoveitol derivatives as novel antidepressants - Tian-Ze Li; Xiao-Yan Huang; Jin-Jin Sun; Chang-An Geng; Xue-Mei Zhang; Ji-Jun Chen (Medicinal Chemistry Research, 2022)

Effect of posaconazole on the concentration of intravenous and oral cyclosporine in patients undergoing hematopoietic stem cell transplantation - Li-E Zhu; Hui-Ping Huang; Yi-Peng Cai; Yan Wang; Bao-Hua Xu; Mao-Bai Liu; Xue-Mei Wu (European Journal of Clinical Pharmacology, 2022)

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

Relationships Between Dietary Patterns and Low-Level Lead Exposure Among Children from Hunan Province of China - Zhi Huang; Xiao-chen Yin; Ming Chen; Mei-ling Li; Bo Chen; Yu-ming Hu (Exposure and Health, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Ectomycorrhizal synthesis between two Tuber species and six tree species: are different host-fungus combinations having dissimilar impacts on host plant growth? - Lan-Lan Huang; Yan-Liang Wang; Alexis Guerin-Laguette; Ran Wang; Peng Zhang; Yong-Mei Li; Fu-Qiang Yu (Mycorrhiza, 2022)

The Role of Long Non-coding RNA, Nuclear Enriched Abundant Transcript 1 (NEAT1) in Cancer and Other Pathologies - Miao Zhang; Jianmin Guo; Lifei Liu; Mei Huang; Yuexuan Li; Samuel Bennett; JiaKe Xu; Jun Zou (Biochemical Genetics, 2022)

A new picrotoxane-type sesquiterpene from Dendrobium nobile Lindl - Pei Wang; Xin Chen; Cai-Hong Cai; Fan-Dong Kong; Sheng-Zhuo Huang; Jing-Zhe Yuan; Xing-Lian Xu; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2022)

A comprehensive exploration on the health risk quantification assessment of soil potentially toxic elements from different sources around large-scale smelting area - Chang-Chen Huang; Li-Mei Cai; Yao-Hui Xu; Luo Jie; Lai-Guo Chen; Guo-Cheng Hu; Hui-Hao Jiang; Xu-Bang Xu; Jing-Xian Mei (Environmental Monitoring and Assessment, 2022)

Strigolactone is involved in nitric oxide-enhanced the salt resistance in tomato seedlings - Huwei Liu; Changxia Li; Mei Yan; Zongxi Zhao; Panpan Huang; Lijuan Wei; Xuetong Wu; Chunlei Wang; Weibiao Liao (Journal of Plant Research, 2022)

Projected change in precipitation forms in the Chinese Tianshan Mountains based on the Back Propagation Neural Network Model - Rui Ren; Xue-mei Li; Zhen Li; Lan-hai Li; Yi-yu Huang (Journal of Mountain Science, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

HMGB1-RAGE Pathway Contributes to the Abnormal Migration of Endogenous Subventricular Zone Neural Progenitors in an Experimental Model of Focal Microgyria - Yi-Wen Mei; Tian-Lan Huang; Xin Chen; Si-Xun Yu; Jie Li; Zhi Zhang; Yang He; Da-qing Guo; Hai-Feng Shu (Journal of Molecular Neuroscience, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Lathyrane diterpenoids from Jatropha podagrica and their antitumor activities in human osteosarcoma cells - Han-Tao Yuan; Qun-Feng Li; Tian Tian; Chun-Yan Zhang; Zou-Qin Huang; Chun-Xiang Fan; Ke Mei; Jie Zhou; Xiao-Xiang Zhai; Si-Bo Li; Jian-Yong Zhu (Natural Product Research, 2021)

Transcriptome-derived microsatellite markers for population diversity analysis in Archidendron clypearia (Jack) I.C. Nielsen - Dandan Li; Mei Li; Fagen Li; Qijie Weng; Changpin Zhou; Shineng Huang; Siming Gan (Molecular Biology Reports, 2021)

Wuchuan bronzes and cinnabar mining immigrants during the Qin and Han Dynasties—new perspectives from typological and lead isotope analysis - Mei Huang; Xiaotong Wu; Xinzhou Chen; Li Tao; Xiaohua Wu; Min Shi; Fei Li; Melissa M. Ritchey; Fang Huang; Zhengyao Jin (Archaeological and Anthropological Sciences, 2021)

Food-grade γ-aminobutyric acid production by immobilized glutamate decarboxylase from Lactobacillus plantarum in rice vinegar and monosodium glutamate system - Li-Li Yao; Jia-Ren Cao; Chang-Jiang Lyu; Fang-Fang Fan; Hong-Peng Wang; Hong-Wei Cao; Jun Huang; Le-He Mei (Biotechnology Letters, 2021)

Astaxanthin Improved the Cognitive Deficits in APP/PS1 Transgenic Mice Via Selective Activation of mTOR - Cuiqin Huang; Caiyan Wen; Mei Yang; An Li; Chongzhu Fan; Danhui Gan; Qin Li; Jiayi Zhao; Lihong Zhu; Daxiang Lu (Journal of Neuroimmune Pharmacology, 2021)

Methane Concentration in the Heartwood of Living Trees and Estimated Methane Emission on Stems in Upland Forests - Zhi-Ping Wang; Huan-Long Li; Hong-Hui Wu; Shi-Jie Han; Jian-Hui Huang; Xi-Mei Zhang; Xing-Guo Han (Ecosystems, 2021)

Dissecting the meteorological and genetic factors affecting rice grain quality in Northeast China - Mojun Chen; Zhao Li; Jie Huang; Yongfeng Yan; Tao Wu; Mingdi Bian; Jinsong Zhou; Yongjun Wang; Yanjie Lyv; Guanghui Hu; Yong-Mei Jin; Kai Huang; et al. (Genes & Genomics, 2021)
Background The Northeast Plain of China, which is an important region for the production of high grain quality rice in China. However, the grain quality of the rice produced varies across this region, even for the same cultivar. Objective In order to explore the meteorological factors that have the greatest influence on quality and the transcriptional level differences between different cultivars and different locations at grain filling stage. Methods We grew eight rice cultivars in three locations in Northeast China during two growing seasons (2017 and 2018). We recorded meteorological conditions, including air temperature, air temperature range, and photosynthetically active radiation (PAR) during the grain-filling stage of each cultivar, and analyzed the grain quality of those eight cultivars. Results Across all eight cultivars, meteorological factors had a stronger effect on eating quality than genotype, while genotype had a stronger effect on milling quality. Of the three environmental factors assessed, PAR was significantly correlated with the most grain quality traits. Using RNA-sequencing analysis, we identified 573 environment-specific DEGs (Differentially Expressed Genes), and 119 genotype-specific DEGs; 11 DEGs were responsive to genotype × environment interactions. These DEGs were involved in many key metabolic processes. Conclusion Our results indicated that interactions among environmental factors, especially PAR, affected rice quality in Northeast China. Further analyses of the DEGs identified herein may provide useful information for future breeding programs aiming to develop high grain quality rice varieties suitable for cultivation across Northeast China.

Evaluation of the RNA extraction methods in different Ginkgo biloba L. tissues - Xiao-lin Zhang; Xiao-li Huang; Jia Li; Mei Mei; Wan-qi Zeng; Xiu-jun Lu (Biologia, 2021)

Maternal exposure to O3 and NO2 may increase the risk of newborn congenital hypothyroidism: a national data-based analysis in China - Cuifang Qi; Li Shang; Wenfang Yang; Liyan Huang; Liren Yang; Juan Xin; Shanshan Wang; Jie Yue; Lingxia Zeng; Mei Chun Chung (Environmental Science and Pollution Research, 2021)
Maternal exposure to air pollution during pregnancy is associated with adverse outcomes in the offspring, but limited studies focused on the impacts of gaseous air pollution on newborn congenital hypothyroidism (CH). Therefore, a national data-based analysis was conducted to explore the association between maternal exposure to gaseous air pollution and the incidence of CH in China. Annual average exposure levels of SO 2 , NO 2 , CO, and O 3 from January 1, 2014, to December 30, 2014, were acquired from the Chinese Air Quality Online Monitoring and Analysis Platform. The annual incidence of newborn CH from October 1, 2014, to September 30, 2015, was collected from the Chinese Maternal and Child Health Surveillance Network. Temperature and toxic metal in wastewater in 2014 were also collected as covariates. Maternal exposure to O 3 and NO 2 in 1 μg/m 3 level increment was positively associated with newborn CH, with an OR of 1.055 (95% CI 1.011, 1.102) and 1.097 (95% CI 1.019, 1.182) after adjusting for covariates completely. Compared with the lowest level of O 3 , maternal exposure to the 4th quartile of O 3 was positively associated with newborn CH (OR 1.393, 95% CI 1.081, 1.794) after adjusting for covariates completely. And the 3rd and 4th quartiles of NO 2 were associated positively with CH (OR 1.576, 95% CI 1.025, 2.424, and OR 1.553, 95% CI 0.999, 2.414, respectively) compared with the lowest level of NO 2 . By fitting the ROC curve, 93.688 μg/m 3 in O 3 might be used as cutoff to predict the incidence of newborn CH in China.

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Restriction of dissolved organic matter on the stabilization of Cu(II) by phosphate - Xiang Ding; Zhongwu Li; Weihua Xu; Mei Huang; Jiajun Wen; Changsheng Jin; Mi Zhou (Environmental Science and Pollution Research, 2021)

Identification and characterization of CONSTANS-like genes from Curcuma alismatifolia - Yuan-Yuan Li; Xiao-Huang Chen; Hui-Wen Yu; Qi-Lin Tian; Luan-Mei Lu (Horticulture, Environment, and Biotechnology, 2021)

Essential oil from Artemisia annua aerial parts: composition and repellent activity against two storage pests - Hong Liu; Shan-Shan Guo; Li Lu; Dian Li; Jun Liang; Zhong-Hui Huang; Yan-Mei Zhou; Wen-Juan Zhang; Shushan Du (Natural Product Research, 2021)

Serotype Distribution and Characteristics of the Minimum Inhibitory Concentrations of Streptococcus pneumoniae Isolated from Pediatric Patients in Kunming, China - Mingbiao Ma; Mei Yuan; Ming Li; Xiaojuan Li; Hailin Huang; Haiping Wang; Jue Li; Tingyi Du; Rongwei Huang (Current Microbiology, 2021)
Streptococcus pneumoniae ( S. pneumoniae ) is the main conditional pathogen of acute respiratory infection in infants, children, and older adults worldwide. It was great significant to identify the epidemic characteristics of serotypes and antibiotic susceptibility for the prevention and treatment of S. pneumoniae diseases. This research assessed the serotype distribution and the minimum inhibitory concentrations (MICs) of S. pneumoniae isolated from pediatric patients to provide information on the epidemiology and antibiotic resistance of S. pneumoniae in Kunming, China. A total of 140 S. pneumoniae isolates were collected from pediatric patients at Kunming Children’s Hospital from January 2016 to October 2017. Serotype identification was done by Quellung reaction and multiplex polymerase chain reaction. MICs were determined by E -test. 140 isolates distributed in 13 types of serotypes. The top-three prevalent serotypes were 19F, 19A, and 6B. The immunization coverage rate of 13-valent pneumococcal conjugate vaccine (PCV) was relatively higher and should be introduced into the vaccination program in the region. MIC 50 of penicillin, ceftriaxone, and levofloxacin was 1 μg/mL. MIC 50 for meropenem and vancomycin was 0.38 μg/mL. MIC 90 of penicillin, ceftriaxone, and levofloxacin was 1.5 μg/mL and that of meropenem and vancomycin was 0.5 μg/mL. The MIC 90 of erythromycin was > 256 μg/mL. In summary, S. pneumoniae had low resistance rates to penicillin, ceftriaxone, levofloxacin, vancomycin, and meropenem, and these antibiotics could be the first-line agents for children with pneumococcal infections in Kunming.

Pseudomonas aeruginosa antitoxin HigA functions as a diverse regulatory factor by recognizing specific pseudopalindromic DNA motifs - Yingjie Song; Guihua Luo; Yibo Zhu; Tao Li; Changcheng Li; Lihui He; Ninglin Zhao; Chang Zhao; Jing Yang; Qin Huang; Xingyu Mu; Xinyue Tang; et al. (Environmental Microbiology, 2021)
Summary Type II toxin‐antitoxin (TA) systems modulate many essential cellular processes in prokaryotic organisms. Recent studies indicate certain type II antitoxins also transcriptionally regulate other genes, besides neutralizing toxin activity. Herein, we investigated the diverse transcriptional repression properties of type II TA antitoxin PaHigA from Pseudomonas aeruginosa . Biochemical and functional analyses showed that PaHigA recognized variable pseudopalindromic DNA sequences and repressed expression of multiple genes. Furthermore, we presented high resolution structures of apo‐PaHigA, PaHigA‐P higBA and PaHigA‐P pa2440 complex, describing how the rearrangements of the HTH domain accounted for the different DNA‐binding patterns among HigA homologues. Moreover, we demonstrated that the N‐terminal loop motion of PaHigA was associated with its apo and DNA‐bound states, reflecting a switch mechanism regulating HigA antitoxin function. Collectively, this work extends our understanding of how the PaHigB/HigA system regulates multiple metabolic pathways to balance the growth and stress response in P. aeruginosa and could guide further development of anti‐TA oriented strategies for pathogen treatment.

Evaluation of the combined effect of sodium persulfate and thermal hydrolysis on sludge dewatering performance - Kai Chen; Jingxin Liu; Simian Huang; Meng Mei; Si Chen; Teng Wang; Jinping Li (Environmental Science and Pollution Research, 2021)

Diterpenoid and triterpenoid glycosides from Clinopodium chinense - Ling-Xia Qu; Yong-Qiao Liu; Yang Wang; Hong Wang; Xue-Li Huang; Mei-Ling Zhang; Yong-Xiao Mou; Tun-Hai Xu; Yin-Di Zhu (Natural Product Research, 2021)

Impact of air pollution exposure during various periods of pregnancy on term birth weight: a large-sample, retrospective population-based cohort study - Li Shang; Liyan Huang; Liren Yang; Longtao Leng; Cuifang Qi; Guilan Xie; Ruiqi Wang; Leqian Guo; Wenfang Yang; Mei Chun Chung (Environmental Science and Pollution Research, 2021)
Previous studies have suggested that maternal exposure to air pollution might affect term birth weight. However, the conclusions are controversial. Birth data of all term newborns born in Xi’an city of Shaanxi, China, from 2015 to 2018 and whose mother lived in Xi’an during pregnancy were selected form the Birth Registry Database. And the daily air quality data of Xi’an city was collected from Chinese Air Quality Online Monitoring and Analysis Platform. Generalized additive models (GAM) and 2-level binary logistic regression models were used to estimate the effects of air pollution exposure on term birth weight, the risk term low birth weight (TLBW), and macrosomia. Finally, 321521 term newborns were selected, including 4369(1.36%) TLBW infants and 24,960 (7.76%) macrosomia. The average pollution levels of PM 2.5 , PM 10 , and NO 2 in Xi’an city from 2015 to 2018 were higher than national limits. During the whole pregnancy, maternal exposure to PM 2.5 , PM 10 , SO 2 , and CO all significantly reduced the term birth weight and increased the risk of TLBW. However, NO 2 and O 3 exposure have significantly increased the term birth weight, and O 3 even increased the risk of macrosomia significantly. Those effects were also observed in the first and second trimesters of pregnancy. But during the third trimester, high level of air quality index (AQI) and maternal exposure to PM 2.5 , PM 10 , SO 2 , NO 2 , and CO increased the term birth weight and the risk of macrosomia, while O 3 exposure was contrary to this effect. The findings suggested that prenatal exposure to air pollution might cause adverse impacts on term birth weight, and the effects varied with trimesters and pollutants, which provides further pieces of evidence for the adverse effects of air pollution exposure in heavy polluted-area on term birth weight.

A review on Cadmium Exposure in the Population and Intervention Strategies Against Cadmium Toxicity - Mei Wang; Zhaofang Chen; Wei Song; Dezi Hong; Lei Huang; Yunhui Li (Bulletin of Environmental Contamination and Toxicology, 2021)

Description of Salinimonas profundi sp. nov., a deep-sea bacterium harboring a transposon Tn6333 - Dao-Feng Zhang; Xi-Wen Cui; Wen-Jun Li; Xiao-Mei Zhang; Hua-Peng Xue; Jian-Ke Huang; Ai-Hua Zhang (Antonie van Leeuwenhoek, 2021)

Spororrminone A and 2- epi -spororrminone A, two new chromones from an endolichenic fungus Sporormiella irregularis - Mei-Juan Huang; Yan-Jun Li; Jia Tang; Guo-Dong Chen; Dan Hu; Wei Xu; Liang-Dong Guo; Xin-Sheng Yao; Hao Gao (Natural Product Research, 2020)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Aluminum and magnesium status during pregnancy and placenta oxidative stress and inflammatory mRNA expression: China Ma’anshan birth cohort study - Jian-Qing Wang; Ya-Bin Hu; Chun-Mei Liang; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Yan Li; Peng Zhu; Jia-Hu Hao; et al. (Environmental Geochemistry and Health, 2020)

LMDS-1, a potential TrkB receptor agonist provides a safe and neurotrophic effect for early-phase Alzheimer’s disease - Chia-Hao Fan; Chia-Wei Lin; Hei-Jen Huang; Guey-Jen Lee-Chen; Ying-Chieh Sun; Wenwei Lin; Chiung-Mei Chen; Kuo-Hsuan Chang; Ming-Tsan Su; Hsiu Mei Hsieh-Li (Psychopharmacology, 2020)

A stacked sparse auto-encoder and back propagation network model for sensory event detection via a flexible ECoG - Oluwagbenga Paul Idowu; Jianping Huang; Yang Zhao; Oluwarotimi William Samuel; Mei Yu; Peng Fang; Guanglin Li (Cognitive Neurodynamics, 2020)

Aureimonas psammosilene sp. nov., isolated from the roots of Psammosilene tunicoides - Mei-Juan Huang; Wu-Lue Huang; Manik Prabhu Narsing Rao; Min Xiao; Hai-Quan Huang; Wen-Jun Li (Archives of Microbiology, 2020)

High throughput solid-phase screening of bacteria with cyclic amino alcohol deamination activity for enantioselective synthesis of chiral cyclic β-amino alcohols - Ya-Wen Chang; Jian-Dong Zhang; Xiao-Xiao Yang; Jing Li; Li-Li Gao; Shuang-Ping Huang; Xing-Mei Guo; Cao-Feng Zhang; Hong-Hong Chang; Jian-He Xu (Biotechnology Letters, 2020)

Study on the uptake of dissolved nitrogen by Oocystis borgei in prawn (Litopenaeus vannamei) aquaculture ponds and establishment of uptake model - Mei Liu; Xiang-Hu Huang; Chang-Ling Li; Binhe Gu (Aquaculture International, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Effects of prenatal exposure to NO2 on children’s neurodevelopment: a systematic review and meta-analysis - Li Shang; Liren Yang; Wenfang Yang; Liyan Huang; Cuifang Qi; Zixuan Yang; Zhuxuan Fu; Mei Chun Chung (Environmental Science and Pollution Research, 2020)
The neurotoxicity of NO 2 exposure is well-known and potentially causes impaired of neural functions. This review aimed to estimate associations between prenatal NO 2 exposure and neurodevelopment for children. Articles published until May 2019 reported prenatal NO 2 exposure and children’s cognition, psychomotor, language, attention, IQ, and behavior function were searched according to all related terms. The main databases we retrieved included PubMed, Web of Science, Embase, and Cochrane Library. Coefficient was extracted, conversed, and synthesized by random effects meta-analysis. Meanwhile, qualitatively describe would be used for some studies which cannot be synthesized quantitatively for lack of quantity or methods inconsistency. Finally, a total of 3848 citations were searched, and only 10 studies were included. We estimated that per 10 μg/m 3 increase of NO 2 during pregnancy was associated with a − 0.76 point decrease in global psychomotor (95% CI, − 1.34, − 0.18) and a − 0.62 point decrease in fine psychomotor for children (95% CI, − 1.09, − 0.16). But no significant association found in general cognitive and language. In addition, through the literature review, it seemed that prenatal exposure to NO 2 might cause adverse impacts on children’s attention, IQ, and different behaviors, but this requires confirmation from further researches. Our study indicated that prenatal exposure to NO 2 seems to be associated with impaired neural development for children, especially for fine psychomotor. However, further studies are needed for determining the effects of prenatal air pollution exposure on attention, IQ, and behavior.

The Secretion from Bone Marrow Mesenchymal Stem Cells Pretreated with Berberine Rescues Neurons with Oxidative Damage Through Activation of the Keap1-Nrf2-HO-1 Signaling Pathway - Caiyan Wen; Cuiqin Huang; Mei Yang; Chongzhu Fan; Qin Li; Jiayi Zhao; Danhui Gan; An Li; Lihong Zhu; Daxiang Lu (Neurotoxicity Research, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Myelin Deficits Caused by Olig2 Deficiency Lead to Cognitive Dysfunction and Increase Vulnerability to Social Withdrawal in Adult Mice - Xianjun Chen; Fei Wang; Jingli Gan; Zhonghua Zhang; Xuejun Liang; Tao Li; Nanxin Huang; Xiaofeng Zhao; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2020)

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Metformin Disrupts Bile Acid Efflux by Repressing Bile Salt Export Pump Expression - Brandy Garzel; Tao Hu; Linhao Li; Yuanfu Lu; Scott Heyward; James Polli; Lei Zhang; Shiew-Mei Huang; Jean-Pierre Raufman; Hongbing Wang (Pharmaceutical Research, 2020)

Tillage practices improve rice yield and soil phosphorus fractions in two typical paddy soils - Waqas Ahmed; Muhammad Qaswar; Huang Jing; Dong Wenjun; Sun Geng; Liu Kailou; Meng Ying; Tang Ao; Sun Mei; Li Chao; Xu Yongmei; Sehrish Ali; et al. (Journal of Soils and Sediments, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

Passivating Effect of Dewatered Sludge and Biochar on As-Contaminated Soil - Ninglin Luo; Jiajun Wen; Zhongwu Li; Mei Huang; Ren Yang (Water, Air, & Soil Pollution, 2020)

In situ meta‐omic insights into the community compositions and ecological roles of hadal microbes in the Mariana Trench - Zhao‐Ming Gao; Jiao‐Mei Huang; Guo‐Jie Cui; Wen‐Li Li; Jun Li; Zhan‐Fei Wei; Jun Chen; Yong‐Zhi Xin; Du‐Si Cai; Ai‐Qun Zhang; Yong Wang (Environmental Microbiology, 2019)
Summary The low temperature and elevated hydrostatic pressure in hadal trenches at water depths below 6000 m render sample collection difficult. Here, in situ hadal water microbial samples were collected from the Mariana Trench and analysed. The hadal microbial communities at different depths were revealed to be consistent and were dominated by heterotrophic Marinimicrobia. Thirty high‐quality metagenome‐assembled genomes (MAGs) were retrieved to represent the major hadal microbes affiliated with 12 prokaryotic phyla. Most of the MAGs were newly reported and probably derived from novel hadal inhabitants as exemplified by a potentially new candidate archaeal phylum in the DPANN superphylum. Metabolic reconstruction indicated that a great number of the MAGs participated in nitrogen and sulfur cycling, in which the nitrification process was driven sequentially by Thaumarchaeota and Nitrospirae and sulfur oxidization by Rhodospirillales in the Alphaproteobacteria class. Moreover, several groups of hadal microbes were revealed to be potential carbon monoxide oxidizers. Metatranscriptomic result highlighted the contribution of Chloroflexi in degrading recalcitrant dissolved organic matter and Marinimicrobia in extracellular protein decomposition. The present work provides an in‐depth view on the hadal microbial communities regarding their endemism and element cycles.

Three new labdane-type diterpenoids from Callicarpa macrophylla Vahl. - Zhen-Hui Wang; Huan-Jun Xu; Yang-Yang Zhai; Lan-Ping Yang; Qiang Li; Mei Huang; Xing-Ying Chen; Wen-Kui Zhang; Yue-Li Meng; Qing-Ling Zhang; Chao Niu; Yan-Ru Zhang (Natural Product Research, 2019)

Two new labdane diterpenoids from aerial parts of Leonurus japonicus and their anti-inflammatory activity - Yu-Mei Hu; Wen-Jun Liu; Meng-Xuan Li; Hai-Bo Li; Tao Jiang; Ning-Bo Cheng; Wen-Zhe Huang; Zhen-Zhong Wang; Hua-Xu Zhu; Wei Xiao (Natural Product Research, 2019)

Comprehensive genetic diagnosis of patients with Duchenne/Becker muscular dystrophy (DMD/BMD) and pathogenicity analysis of splice site variants in the DMD gene - Yan-mei Yang; Kai Yan; Bei Liu; Min Chen; Li-ya Wang; Ying-zhi Huang; Ye-qing Qian; Yi-xi Sun; Hong-ge Li; Min-yue Dong (Journal of Zhejiang University-SCIENCE B, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Synthesis of oleanolic acid/ursolic acid/glycyrrhetinic acid-hydrogen sulfide donor hybrids and their antitumor activity - Li-xin Sheng; Jia-yan Huang; Chun-mei Liu; Ju-zheng Zhang; Ke-guang Cheng (Medicinal Chemistry Research, 2019)

Biodiversity and antifouling activity of fungi associated with two soft corals from the South China Sea - Xiao-Yong Zhang; Hui-Li Hao; Stanley Chun Kwan Lau; Huai-You Wang; Yu Han; Li-Mei Dong; Ri-Ming Huang (Archives of Microbiology, 2019)

Lycopene protects against t-BHP-induced neuronal oxidative damage and apoptosis via activation of the PI3K/Akt pathway - Cuiqin Huang; Caiyan Wen; Mei Yang; Danhui Gan; Chongzhu Fan; An Li; Qin Li; Jiayi Zhao; Lihong Zhu; Daxiang Lu (Molecular Biology Reports, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

Copy number variation of bovine SHH gene is associated with body conformation traits in Chinese beef cattle - Mei Liu; Bo Li; Tao Shi; Yongzhen Huang; George E. Liu; Xianyong Lan; Chuzhao Lei; Hong Chen (Journal of Applied Genetics, 2019)

Chronic low dose of AM404 ameliorates the cognitive impairment and pathological features in hyperglycemic 3xTg-AD mice - Hei-Jen Huang; Shu-Ling Chen; Hsin-Yu Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Hsiu Mei Hsieh-Li; Ming-Tsan Su (Psychopharmacology, 2019)

A miR-18a binding-site polymorphism in CDC42 3′UTR affects CDC42 mRNA expression in placentas and is associated with litter size in pigs - Ruize Liu; Dadong Deng; Xiangdong Liu; Yujing Xiao; Ji Huang; Feiyu Wang; Xinyun Li; Mei Yu (Mammalian Genome, 2019)

Genomics insights into ecotype formation of ammonia‐oxidizing archaea in the deep ocean - Yong Wang; Jiao‐Mei Huang; Guo‐Jie Cui; Takuro Nunoura; Yoshihiro Takaki; Wen‐Li Li; Jun Li; Zhao‐Ming Gao; Ken Takai; Ai‐Qun Zhang; Ramunas Stepanauskas (Environmental Microbiology, 2019)
Summary Various lineages of ammonia‐oxidizing archaea (AOA) are present in deep waters, but the mechanisms that determine ecotype formation are obscure. We studied 18 high‐quality genomes of the marine group I AOA lineages (alpha, gamma and delta) from the Mariana and Ogasawara trenches. The genomes of alpha AOA resembled each other, while those of gamma and delta lineages were more divergent and had even undergone insertion of some phage genes. The instability of the gamma and delta AOA genomes could be partially due to the loss of DNA polymerase B ( polB) and methyladenine DNA glycosylase ( tag ) genes responsible for the repair of point mutations. The alpha AOA genomes harbour genes encoding a thrombospondin‐like outer membrane structure that probably serves as a barrier to gene flow. Moreover, the gamma and alpha AOA lineages rely on vitamin B 12 ‐independent MetE and B 12 ‐dependent MetH, respectively, for methionine synthesis. The delta AOA genome contains genes involved in uptake of sugar and peptide perhaps for heterotrophic lifestyle. Our study provides insights into co‐occurrence of cladogenesis and anagenesis in the formation of AOA ecotypes that perform differently in nitrogen and carbon cycling in dark oceans.

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Uptake of Urea Nitrogen by Oocystis borgei in Prawn (Litopenaeus vannamei) Aquaculture Ponds - Mei Liu; Xianghu Huang; Rui Zhang; Changling Li; Binhe Gu (Bulletin of Environmental Contamination and Toxicology, 2018)

Nocardia zhihengii sp. nov., an actinobacterium isolated from rhizosphere soil of Psammosilene tunicoides - Mei-Juan Huang; Min Xiao; Manik Prabhu Narsing Rao; Tao Cheng; Yan-Yu Yang; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Hai-Quan Huang; Wen-Jun Li (Antonie van Leeuwenhoek, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Factors regulating carbon sinks in mangrove ecosystems - Shi‐Bo Li; Po‐Hung Chen; Jih‐Sheng Huang; Mei‐Li Hsueh; Li‐Yung Hsieh; Chen‐Lu Lee; Hsing‐Juh Lin (Global Change Biology, 2018)
Mangroves are recognized as one of the richest carbon storage systems. However, the factors regulating carbon sinks in mangrove ecosystems are still unclear, particularly in the subtropical mangroves. The biomass, production, litterfall, detrital export and decomposition of the dominant mangrove vegetation in subtropical ( Kandelia obovata ) and tropical ( Avicennia marina ) Taiwan were quantified from October 2011 to July 2014 to construct the carbon budgets. Despite the different tree species, a principal component analysis revealed the site or environmental conditions had a greater influence than the tree species on the carbon processes. For both species, the net production (NP) rates ranged from 10.86 to 27.64 Mg C ha −1 year −1 and were higher than the global average rate due to the high tree density. While most of the litterfall remained on the ground, a high percentage (72%–91%) of the ground litter decomposed within 1 year and fluxed out of the mangroves. However, human activities might cause a carbon flux into the mangroves and a lower NP rate. The rates of the organic carbon export and soil heterotrophic respiration were greater than the global mean values and those at other locations. Only a small percentage (3%–12%) of the NP was stored in the sediment. The carbon burial rates were much lower than the global average rate due to their faster decomposition, indicating that decomposition played a critical role in determining the burial rate in the sediment. The summation of the organic and inorganic carbon fluxes and soil heterotrophic respiration well exceeded the amount of litter decomposition, indicating an additional source of organic carbon that was unaccounted for by decomposition in the sediment. Sediment‐stable isotope analyses further suggest that the trapping of organic matter from upstream rivers or adjacent waters contributed more to the mangrove carbon sinks than the actual production of the mangrove trees.

High-resolution melting-based TILLING of γ ray-induced mutations in rice - Shan Li; Song-mei Liu; Hao-wei Fu; Jian-zhong Huang; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2018)

Intermittent micro-aeration control of methane emissions from an integrated vertical-flow constructed wetland during agricultural domestic wastewater treatment - Xiaoling Liu; Ke Zhang; Liangqian Fan; Hongbing Luo; Mingshu Jiang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Guozhu He; Jingting Wang; Aiping Pu (Environmental Science and Pollution Research, 2018)

Combination of NAD+ and NADPH Offers Greater Neuroprotection in Ischemic Stroke Models by Relieving Metabolic Stress - Qiao Huang; Meiling Sun; Mei Li; Dingmei Zhang; Feng Han; Jun Chao Wu; Kohji Fukunaga; Zhong Chen; Zheng-Hong Qin (Molecular Neurobiology, 2018)

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

Risk factors and clinical outcomes of hypervirulent Klebsiella pneumoniae induced bloodstream infections - Jiayang Li; Jianan Ren; Weiping Wang; Gefei Wang; Guosheng Gu; Xiuwen Wu; Ying Wang; Mei Huang; Jieshou Li (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Knockdown of PRMT1 suppresses IL-1β-induced cartilage degradation and inflammatory responses in human chondrocytes through Gli1-mediated Hedgehog signaling pathway - Lei Xia; Hong-Xing Zhang; Mei-Li Xing; Yu-Ben Xu; Peng Li; Liang-Ku Huang; Jie Bai; Zhao Tian; Zan-Dong Zhao (Molecular and Cellular Biochemistry, 2018)

Links between Western Pacific Subtropical High and vegetation growth in China - Mei Huang; Man Hao; Shaoqiang Wang; Li Dan; Fengxue Gu; Zhaosheng Wang; He Gong (Journal of Geographical Sciences, 2018)

20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol negatively regulates activation of STAT3 and ERK pathways and exhibits anti-cancer effects in HepG2 cells - Hui-Han Ai; Zi-Long Zhou; Lu-Guo Sun; Mei-Ting Yang; Wei Li; Chun-Lei Yu; Zhen-Bo Song; Yan-Xin Huang; Yin Wu; Lei Liu; Xiao-Guang Yang; Yu-Qing Zhao; et al. (Apoptosis, 2017)

Inhibition of P2X7 Receptor Ameliorates Nuclear Factor-Kappa B Mediated Neuroinflammation Induced by Status Epilepticus in Rat Hippocampus - Cheng Huang; Xiao-sa Chi; Rui Li; Xin Hu; Hai-xia Xu; Jin-mei Li; Dong Zhou (Journal of Molecular Neuroscience, 2017)

Assessment of germling ability of the introduced marine brown alga, Sargassum horneri, in Northern Taiwan - Showe-Mei Lin; Roger Huang; Hisao Ogawa; Li-Chia Liu; Yi-Chi Wang; Yushan Chiou (Journal of Applied Phycology, 2017)

Two new biphenyls from the stems of Garcinia tetralata - Bing-Kun Ji; Xue-Mei Gao; Di Cui; Shan-Shan Wang; Wen-Zhong Huang; Yin-Ke Li; Shuang-Xi Mei; Zhi Yang; Gan-Peng Li; Meng-Yuan Jiang; Yong-Hui He; Zhi-Yong Jiang; et al. (Natural Product Research, 2017)

Comparison of two matrix-assisted laser desorption ionization-time of flight mass spectrometry systems for the identification of clinical filamentous fungi - Yanfei Huang; Mingxin Zhang; Min Zhu; Mei Wang; Yufeng Sun; Haitong Gu; Jingjing Cao; Xue Li; Shaoya Zhang; Jinglin Wang; Xinxin Lu (World Journal of Microbiology and Biotechnology, 2017)

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

Individual and combined inhibition of phenol and thiocyanate on microbial activity of partial nitritation - Qiong Guo; Zhi-Jian Shi; Chen-Chen Yang; Mei Huang; Jia-Li Xu; Yi-Qun Xu; Wei-Min Ni; Ren-Cun Jin (Environmental Science and Pollution Research, 2017)

Characterization of 29 highly polymorphic microsatellite markers for golden snub-nosed monkey (Rhinopithecus roxellana) - Yan-Mei Duan; Kang Huang; Xiao-Guang QI; Bao-Guo LI (Conservation Genetics Resources, 2017)

Effect of compatible herbs on the pharmacokinetics of effective components of Panax notoginseng in Fufang Xueshuantong Capsule - Huan-huan Pang; Meng-yi Li; Yuan Wang; Min-ke Tang; Chang-hua Ma; Jian-mei Huang (Journal of Zhejiang University-SCIENCE B, 2017)

Vegetation carbon sequestration in Chinese forests from 2010 to 2050 - Nianpeng He; Ding Wen; Jianxing Zhu; Xuli Tang; Li Xu; Li Zhang; Huifeng Hu; Mei Huang; Guirui Yu (Global Change Biology, 2017)
Forests store a large part of the terrestrial vegetation carbon (C) and have high C sequestration potential. Here, we developed a new forest C sequestration ( FCS ) model based on the secondary succession theory, to estimate vegetation C sequestration capacity in China's forest vegetation. The model used the field measurement data of 3161 forest plots and three future climate scenarios. The results showed that logistic equations provided a good fit for vegetation biomass with forest age in natural and planted forests. The FCS model has been verified with forest biomass data, and model uncertainty is discussed. The increment of vegetation C storage in China's forest vegetation from 2010 to 2050 was estimated as 13.92 Pg C, while the average vegetation C sequestration rate was 0.34 Pg C yr −1 with a 95% confidence interval of 0.28–0.42 Pg C yr −1 , which differed significantly between forest types. The largest contributor to the increment was deciduous broadleaf forest (37.8%), while the smallest was deciduous needleleaf forest (2.7%). The vegetation C sequestration rate might reach its maximum around 2020, although vegetation C storage increases continually. It is estimated that vegetation C sequestration might offset 6–8% of China's future emissions. Furthermore, there was a significant negative relationship between vegetation C sequestration rate and C emission rate in different provinces of China, suggesting that developed provinces might need to compensate for undeveloped provinces through C trade. Our findings will provide valuable guidelines to policymakers for designing afforestation strategies and forest C trade in China.

Detection of chlorophylls in spores of seven ferns - Mei-Hwei Tseng; Kuei-Huei Lin; Yi-Jia Huang; Ya-Lan Chang; Sheng-Cih Huang; Li-Yaung Kuo; Yao-Moan Huang (Journal of Plant Research, 2017)

Isolation, chemical characterization, and immunomodulatory activity of naturally acetylated hemicelluloses from bamboo shavings - Ju-qing Huang; Rui-ting Qi; Mei-rong Pang; Cong Liu; Guang-yu Li; Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

A new hetero dimeric terpenoid derivative, japonicaside C, from the flower buds of Lonicera japonica - Hai-Bo Li; Yang Yu; Yu-Dan Mei; Zhao-Qing Meng; Zhen-Zhong Wang; Wen-Zhe Huang; Wei Xiao; Xin-Sheng Yao (Natural Product Research, 2017)

Effect of land use pattern change from paddy soil to vegetable soil on the adsorption-desorption of cadmium by soil aggregates - Qiu Zhang; Zhongwu Li; Bin Huang; Ninglin Luo; Lingzhi Long; Mei Huang; Xiuqing Zhai; Guangming Zeng (Environmental Science and Pollution Research, 2017)

Compost as a Soil Amendment to Remediate Heavy Metal-Contaminated Agricultural Soil: Mechanisms, Efficacy, Problems, and Strategies - Mei Huang; Yi Zhu; Zhongwu Li; Bin Huang; Ninglin Luo; Chun Liu; Guangming Zeng (Water, Air, & Soil Pollution, 2016)

Genome-Wide Analysis of the R2R3 MYB Subfamily Genes in Lotus (Nelumbo nucifera) - Jiao Deng; Ming Li; Longyu Huang; Mei Yang; Pingfang Yang (Plant Molecular Biology Reporter, 2016)

Streptomyces zhihengii sp. nov., isolated from rhizospheric soil of Psammosilene tunicoides - Mei-Juan Huang; Jing-Jing Fei; Nimaichand Salam; Chang-Jin Kim; Wael N. Hozzein; Min Xiao; Hai-Quan Huang; Wen-Jun Li (Archives of Microbiology, 2016)

Establishing an efficient gene-targeting system in an itaconic-acid producing Aspergillus terreus strain - Xuenian Huang; Mei Chen; Jianjun Li; Xuefeng Lu (Biotechnology Letters, 2016)

Genomic characterization of symbiotic mycoplasmas from the stomach of deep‐sea isopod bathynomus sp - Yong Wang; Jiao‐Mei Huang; Shao‐Lu Wang; Zhao‐Ming Gao; Ai‐Qun Zhang; Antoine Danchin; Li‐Sheng He (Environmental Microbiology, 2016)
Deep‐sea isopod scavengers such as Bathynomus sp. are able to live in nutrient‐poor environments, which is likely attributable to the presence of symbiotic microbes in their stomach. In this study we recovered two draft genomes of mycoplasmas, Bg1 and Bg2, from the metagenomes of the stomach contents and stomach sac of a Bathynomus sp. sample from the South China Sea (depth of 898 m). Phylogenetic trees revealed a considerable genetic distance to other mycoplasma species for Bg1 and Bg2. Compared with terrestrial symbiotic mycoplasmas, the Bg1 and Bg2 genomes were enriched with genes encoding phosphoenolpyruvate‐dependent phosphotransferase systems (PTSs) and sodium‐driven symporters responsible for the uptake of sugars, amino acids and other carbohydrates. The genome of mycoplasma Bg1 contained sialic acid lyase and transporter genes, potentially enabling the bacteria to attach to the stomach sac and obtain organic carbons from various cell walls. Both of the mycoplasma genomes contained multiple copies of genes related to proteolysis and oligosaccharide degradation, which may help the host survive in low‐nutrient conditions. The discovery of the different types of mycoplasma bacteria in the stomach of this deep‐sea isopod affords insights into symbiotic model of deep‐sea animals and genomic plasticity of mycoplasma bacteria.

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

The proteome and phosphoproteome of maize pollen uncovers fertility candidate proteins - Qing Chao; Zhi-fang Gao; Yue-feng Wang; Zhe Li; Xia-he Huang; Ying-chun Wang; Ying-chang Mei; Biligen-gaowa Zhao; Liang Li; Yu-bo Jiang; Bai-chen Wang (Plant Molecular Biology, 2016)

Calpain-Dependent ErbB4 Cleavage Is Involved in Brain Ischemia-Induced Neuronal Death - Ying-mei Lu; Yin-ping Gao; Rong-rong Tao; Mei-hua Liao; Ji-yun Huang; Gang Wu; Feng Han; Xiao-ming Li (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Chemotherapeutic agent CPT-11 eliminates peritoneal resident macrophages by inducing apoptosis - Mei-Yun Huang; Hao Pan; Yi-Dan Liang; Hong-Xia Wei; Li-Hui Xu; Qing-Bing Zha; Xian-Hui He; Dong-Yun Ouyang (Apoptosis, 2016)

Complete genome sequence of a distinct calla lily chlorotic spot virus isolated in mainland China - Ye Xu; Si-bo Wang; Yong-zhong Li; Hong-zheng Tao; Ya-ning Huang; Bao-wei Wu; Yu-mei Dong; John Hu; Ya-ting Liu (Archives of Virology, 2016)

PPR protein PDM1/SEL1 is involved in RNA editing and splicing of plastid genes in Arabidopsis thaliana - Hong-Dao Zhang; Yong-Lan Cui; Chao Huang; Qian-Qian Yin; Xue-Mei Qin; Te Xu; Xiao-Fang He; Yi Zhang; Zi-Ran Li; Zhong-Nan Yang (Photosynthesis Research, 2015)

Social Isolation During Adolescence Strengthens Retention of Fear Memories and Facilitates Induction of Late-Phase Long-Term Potentiation - Ji-Hong Liu; Qiang-Long You; Mei-Dan Wei; Qian Wang; Zheng-Yi Luo; Song Lin; Lang Huang; Shu-JI Li; Xiao-Wen Li; Tian-Ming Gao (Molecular Neurobiology, 2015)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

Estimating the tendency of motor unit recruitment during steady-hold and rapid contractions using surface EMG and Turns-amplitude analysis - Li-Ling Pan; Chung-Huang Yu; Mei-Wun Tsai; Shun-Hwa Wei; Li-Wei Chou (European Journal of Applied Physiology, 2015)

Up-regulation of SPOCK1 induces epithelial–mesenchymal transition and promotes migration and invasion in esophageal squamous cell carcinoma - Xiaopeng Song; Ping Han; Jingmei Liu; Yunwu Wang; Dongxiao Li; Jiayi He; Jin Gong; Mengke Li; Wei Tu; Wei Yan; Mei Liu; Huanjun Huang; et al. (Journal of Molecular Histology, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Molecular cloning and characterization of a pathogenesis-related protein SmPR10-1 from Salvia miltiorrhiza - Le Zhao; Li-gang Ma; Zhi-shuang Wang; Mei-lan Chen; Ye Shen; Lu-qi Huang (Acta Physiologiae Plantarum, 2015)

Infrared ultraspectral signature classification based on a restricted Boltzmann machine with sparse and prior constraints - Xiaoguang Mei; Yong Ma; Fan Fan; Chang Li; Chengyin Liu; Jun Huang; Jiayi Ma (International Journal of Remote Sensing, 2015)

Longitudinal changes of dopamine transporters in heroin users during abstinence - Shasha Xu; Ying Liu; Yu Li; Yangping Deng; Yiyun Huang; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Zhirui Guo; Mei Han; Xingdang Liu; et al. (Psychopharmacology, 2015)

Fluorofenidone protects against renal fibrosis by inhibiting STAT3 tyrosine phosphorylation - Juan Tang; Chun-yan Liu; Miao-miao Lu; Jing Zhang; Wen-juan Mei; Wen-jun Yang; Yan-yun Xie; Ling Huang; Zhang-zhe Peng; Qiong-jing Yuan; Ji-shi Liu; Gao-yun Hu; et al. (Molecular and Cellular Biochemistry, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Distribution of Yeast Isolates from Invasive Infections and Their In Vitro Susceptibility to Antifungal Agents: Evidence from 299 Cases in a 3-Year (2010 to 2012) Surveillance Study - Wei Li; Yu-an Hu; Fang-qiu Li; Li-ning Shi; Hai-feng Shao; Mei Huang; Ying Wang; Dan-dan Han; Hong Liao; Chun-fang Ma; Guo-yong Zhang (Mycopathologia, 2015)

Study on runoff simulation of the upstream of Minjiang River under future climate change scenarios - Shifeng Huang; Wenbin Zang; Mei Xu; Xiaotao Li; Xuecheng Xie; Zhongmin Li; Jisheng Zhu (Natural Hazards, 2015)

Drug-Induced Modulation of T Lymphocytes as a Potential Mechanism of Susceptibility to Infections in Patients with Multiple Myeloma During Bortezomib Therapy - Juan Li; Ying Li; Beihui Huang; Dong Zheng; Mei Chen; Zhenhai Zhou (Cell Biochemistry and Biophysics, 2015)
Bortezomib is effective in the therapy of multiple myeloma (MM), but causes infections that are different from those associated with conventional chemotherapy. It is important to identify the risk factors that facilitate infections associated with bortezomib therapy. In the present report, we sought to (1) define the features of the infections associated with this therapy and (2) identify the immune mechanisms responsible for the observed susceptibility to these infections. We first retrospectively analyzed the clinical data of 143 patients who had received bortezomib therapy for MM. We then prospectively assessed the modulation of T lymphocyte status during this therapy, and evaluated potential relationships between infections and T lymphocyte changes. The infection rates peaked during the first cycle of bortezomib therapy (47.6 %) in patients with MM ( p < 0.05 vs. subsequent cycles). Bortezomib therapy was associated with higher incidence rates of viral and fungal infections (15.8 %, p < 0.05 vs. conventional chemotherapy). In addition, patients with the IgG immunophenotype showed higher bacterial and viral infection rates (respectively, p = 0.008 and 0.009). The T lymphocyte numbers significantly decreased after bortezomib therapy ( p < 0.05), and the same was true for the Th1/Th2 ratio ( p < 0.01). Patients with MM who have decreased lymphocyte counts, while on bortezomib therapy are more likely to develop bacterial or viral infections. In addition, an imbalance in T lymphocyte subsets is also associated with bacterial or viral infections in these patients.

Radial oxygen loss has different effects on the accumulation of total mercury and methylmercury in rice - Xun Wang; Bing Li; Nora Fung-Yee Tam; Lu Huang; Xiaoli Qi; Hongbin Wang; Zhihong Ye; Mei Meng; Jianbo Shi (Plant and Soil, 2014)

Risk for estrogen-dependent diseases in relation to phthalate exposure and polymorphisms of CYP17A1 and estrogen receptor genes - Po-Chin Huang; Wan-Fen Li; Pao-Chi Liao; Chien-Wen Sun; Eing-Mei Tsai; Shu-Li Wang (Environmental Science and Pollution Research, 2014)

Identification of a novel SHOX mutation in a Chinese family with isolated Madelung deformity - LIBIN MEI; YANRU HUANG; QIAN PAN; HAOXIAN LI; DESHENG LIANG; LINGQIAN WU (Journal of Genetics, 2014)

Isolation and characterization of twenty-five polymorphic microsatellite markers in Siniperca scherzeri Steindachner and cross-species amplification - WEI HUANG; XU-FANG LIANG; CHUN-MEI QU; JI LI; LIANG CAO (Journal of Genetics, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Characterization of Arabidopsis Tubby-like proteins and redundant function of AtTLP3 and AtTLP9 in plant response to ABA and osmotic stress - Yan Bao; Wei-Meng Song; Yan-Li Jin; Chun-Mei Jiang; Yang Yang; Bei Li; Wei-Jie Huang; Hua Liu; Hong-Xia Zhang (Plant Molecular Biology, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Gene Expressing Difference in Sclerotial Formation of Morchella conica - Li-Jiao Chen; Hong-Mei Chai; Wei-Min Chen; Xing-Qi Huang; Yong-Chang Zhao (Indian Journal of Microbiology, 2014)

The Role of the QseC Quorum-Sensing Sensor Kinase in Epinephrine-Enhanced Motility and Biofilm Formation by Escherichia coli - Kun Yang; Jun Meng; Yun-chao Huang; Lian-hua Ye; Guang-jian Li; Jie Huang; Hua-mei Chen (Cell Biochemistry and Biophysics, 2014)

Bombyx mori Nucleopolyhedrovirus ORF101 Encodes a Budded Virus Envelope Associated Protein - Huiqing Chen; Mei Li; Guoping Huang; Weijun Mai; Keping Chen; Yajing Zhou (Current Microbiology, 2014)

Variations of culturable thermophilic microbe numbers and bacterial communities during the thermophilic phase of composting - Rong Li; Linzhi Li; Rong Huang; Yifei Sun; Xinlan Mei; Biao Shen; Qirong Shen (World Journal of Microbiology and Biotechnology, 2014)

Functionalized Magnetic Microparticles for Fast and Efficient Removal of Textile Dyes from Aqueous Solution - Qing-Song Zhao; Yan-Feng Huang; Ying Li; Ji-Mei Zhang; Hong-Yi Wang (Water, Air, & Soil Pollution, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Synthesis, characterization, and biological studies of emissive rhenium–glutamine conjugates - Rachel Huang; Graeme Langille; Ravanjir K. Gill; Cindy Mei Jin Li; Yuji Mikata; May Q. Wong; Donald T. Yapp; Tim Storr (JBIC Journal of Biological Inorganic Chemistry, 2013)

Uptake of arsenic species by turnip ( Brassica rapa L.) and lettuce ( Lactuca sativa L.) treated with roxarsone and its metabolites in chicken manure - Lian Xi Huang; Li Xian Yao; Zhao Huan He; Chang Min Zhou; Guo Liang Li; Bao Mei Yang; Ying Fen Li (Food Additives & Contaminants: Part A, 2013)

Genome-Wide Phylogenetic Analysis of Stress-Activated Protein Kinase Genes in Rice (OsSAPKs) and Expression Profiling in Response to Xanthomonas oryzae pv. oryzicola Infection - Mei-Rong Xu; Li-Yu Huang; Fan Zhang; Ling-Hua Zhu; Yong-Li Zhou; Zhi-Kang Li (Plant Molecular Biology Reporter, 2013)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

The Negative Regulator OsSDS1 Significantly Reduces Salt and Drought Tolerance in Transgenic Arabidopsis - Guoyun Xu; Mingjuan Li; Mei Huang; Yanchun Cui; Manling Wang; Xinjie Xia (Plant Molecular Biology Reporter, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Astrocyte-Derived Sonic Hedgehog Contributes to Angiogenesis in Brain Microvascular Endothelial Cells via RhoA/ROCK Pathway After Oxygen–Glucose Deprivation - Quan-Wei He; Yuan-Peng Xia; Sheng-Cai Chen; Yong Wang; Ming Huang; Yan Huang; Jian-Yong Li; Ya-Nan Li; Yuan Gao; Ling Mao; Yuan-Wu Mei; Bo Hu (Molecular Neurobiology, 2013)

Expression pattern of genes involved in maternal immune regulation during the peri-implantation and midgestation in Meishan pigs - Xiaoping Li; Zongping Zhang; Jiangnan Huang; Lijie Su; Mengjin Zhu; Mei Yu (Genes & Genomics, 2013)

Levosimendan versus dobutamine in critically ill patients: a meta-analysis of randomized controlled trials - Xuan Huang; Shu Lei; Mei-fei Zhu; Rong-lin Jiang; Li-quan Huang; Guo-lian Xia; Yi-hui Zhi (Journal of Zhejiang University-SCIENCE B, 2013)

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives - Yan Zeng; Lan-Ping Guo; Bao-Dong Chen; Zhi-Peng Hao; Ji-Yong Wang; Lu-Qi Huang; Guang Yang; Xiu-Ming Cui; Li Yang; Zhao-Xiang Wu; Mei-Lan Chen; Yan Zhang (Mycorrhiza, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Effects of Huangqi and bear bile on recurrent parotitis in children: a new clinical approach - Wen-hua Ruan; Mei-li Huang; Xiao-lei He; Feng Zhang; Hai-biao Tao (Journal of Zhejiang University-SCIENCE B, 2013)

Regional and cell-type specific distribution of HDAC2 in the adult mouse brain - Zhi-Gang Yao; Ling Zhang; Lan Huang; Hua Zhu; Ying Liu; Chun-Mei Ma; Shu-Li Sheng; Chuan Qin (Brain Structure and Function, 2013)

Genome characterization of a novel porcine bocavirus - Wan-zhu Yang; Jie-mei Yu; Jin-song Li; Wei-xia Cheng; Can-ping Huang; Zhao-jun Duan (Archives of Virology, 2012)

Water surface variations monitoring and flood hazard analysis in Dongting Lake area using long-term Terra/MODIS data time series - Shifeng Huang; Jinggang Li; Mei Xu (Natural Hazards, 2012)

Scattering spectrum properties and their relationship to biogeochemical parameters: a case study in Taihu Lake - Chang-Chun Huang; Yun-Mei Li; Qiao Wang; De-Yong Sun; Cheng-Feng Le; Kun Shi (Limnology, 2012)

Advances in study of ginsenoside biosynthesis pathway in Panax ginseng C. A. Meyer - Juan Wang; Wen-Yuan Gao; Jian Zhang; Bei-Mei Zuo; Li-Ming Zhang; Lu-Qi Huang (Acta Physiologiae Plantarum, 2012)

Catalytic characteristics of plant-esterase from wheat flour - Chang-jun Hou; Kun He; Li-min Yang; Dan-qun Huo; Mei Yang; Shun Huang; Liang Zhang; Cai-hong Shen (World Journal of Microbiology and Biotechnology, 2012)

Production of ginsenoside and polysaccharide by two-stage cultivation of Panax quinquefolium L. cells - Juan Wang; Wen-Yuan Gao; Jian Zhang; Bei-Mei Zuo; Li-Ming Zhang; Lu-Qi Huang (In Vitro Cellular & Developmental Biology - Plant, 2012)

Gambogenic acid-induced time- and dose-dependent growth inhibition and apoptosis involving Akt pathway inactivation in U251 glioblastoma cells - Hong-Bo Chen; Lan-Zhen Zhou; Lin Mei; Xiao-Jun Shi; Xiao-Shan Wang; Qing-Lin Li; Laiqiang Huang (Journal of Natural Medicines, 2012)

Nasopharyngeal carcinoma: Advances in genomics and molecular genetics - ZhaoYang Zeng; HongBin Huang; WenLing Zhang; Bo Xiang; Ming Zhou; YanHong Zhou; Jian Ma; Mei Yi; XiaYu Li; XiaoLing Li; Wei Xiong; GuiYuan Li (Science China Life Sciences, 2011)

Identification of QTL genes for BMD variation using both linkage and gene-based association approaches - Gloria Hoi-Yee Li; Ching-Lung Cheung; Su-Mei Xiao; Kam-Shing Lau; Yi Gao; Cora H. Bow; Qing-Yang Huang; Pak-Chung Sham; Annie Wai-Chee Kung (Human Genetics, 2011)

A study on the effects of the surrounding faults on water loss in the Zoige Wetland, China - Mei Li; Rui Xu; Wendian Huang; Hailong Sun; Lin Luo (Journal of Mountain Science, 2011)

A neural-network model to retrieve CDOM absorption from in situ measured hyperspectral data in an optically complex lake: Lake Taihu case study - De Yong Sun; Yun Mei Li; Qiao Wang; Heng Lu; Cheng Feng Le; Chang Chun Huang; Shao Qi Gong (International Journal of Remote Sensing, 2011)

Transgenic watermelon lines expressing the nucleocapsid gene of Watermelon silver mottle virus and the role of thiamine in reducing hyperhydricity in regenerated shoots - Ying-Chih Huang; Chu-Hui Chiang; Chin-Mei Li; Tsong-Ann Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

A novel thermostable phytase from the fungus Aspergillus aculeatus RCEF 4894: gene cloning and expression in Pichia pastoris - Zhong-You Ma; Shun-Chang Pu; Jing-Jing Jiang; Bo Huang; Mei-Zhen Fan; Zeng-Zhi Li (World Journal of Microbiology and Biotechnology, 2011)

Determination of Trace Deoxyribonucleic Acid by Using Fluorescein Isothiocyanate-Phenosafranine as a Double-Luminescent Phosphorescence Probe - Jia-Ming Liu; Xiao-Mei Huang; Zhen-Bo Liu; Fei-Ming Li; Li-Ping Lin; Xin-Xing Wang; Chang-Qing Lin; Ya-Hong Huang; Zhi-Ming Li; Shao-Qin Lin (Journal of Fluorescence, 2011)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

A fibrillar form of fibronectin induces apoptosis by activating SHP-2 and stress fiber formation - Chun-Yung Huang; Chi-Ming Liang; Chiao-Li Chu; Jei-Ming Peng; Shu-Mei Liang (Apoptosis, 2010)

Sensitive Phosphorimetric Determination of Bumetanide in Human Urine with Its Inhibition Effect on the Formation of [Fe-morin] 3+ Complex - Li-Qing Zeng; Jia-Ming Liu; Fei-Ming Li; Xiao-Mei Huang; Li-Ping Lin; Xin-Xing Wang; Li-Hong Zhang; Chang-Qing Lin (Journal of Fluorescence, 2010)

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells - Yun-mei Yang; Wei-dong Huang; Qiang-min Xie; Zhe-rong Xu; Qi-jiang Zhao; Xi-mei Wu; Fen-fen Li; Xin-wei Dong (Inflammation Research, 2010)

Ten novel tetranucleotide microsatellite DNA markers from Asiatic black bear, Ursus thibetanus - Chih-Chin Shih; Chuan-Chin Huang; Shou-Hsien Li; Mei-Hsiu Hwang; Ling-Ling Lee (Conservation Genetics, 2009)

Polymorphisms in arsenic metabolism genes, urinary arsenic methylation profile and cancer - Chi-Jung Chung; Yu-Mei Hsueh; Chyi-Huey Bai; Yung-Kai Huang; Ya-Li Huang; Mo-Hsiung Yang; Chien-Jen Chen (Cancer Causes & Control, 2009)

Preparation and application of rat myostatin antiserum - Li Huang; Li-Li Wang; Mei Liu; Xiao-Song Gu (Neuroscience Bulletin, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

Transformation of sugarcane with ACC oxidase antisense gene - Ai-Qin Wang; Wei-Qing Dong; Yuan-Wen Wei; Cheng-Mei Huang; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2009)

Determination of Bioactive Matter by Affinity Adsorption Solid Substrate–Room Temperature Phosphorimetry Based on Lectin Labeled with Self-ordered Ring of Eosin Y - Jia-Ming Liu; Zhen-Bo Liu; Wen-Qi Li; Xiao-Mei Huang; Li-Qing Zeng; Jian Sha; Fei-Ming Li (Journal of Fluorescence, 2009)

Arsenic exposure, urinary arsenic speciation, and the incidence of urothelial carcinoma: a twelve-year follow-up study - Yung-Kai Huang; Ya-Li Huang; Yu-Mei Hsueh; Mo-Hsiung Yang; Meei-Maan Wu; Shu-Yuan Chen; Ling-I Hsu; Chien-Jen Chen (Cancer Causes & Control, 2008)

Compensatory growth of Chinese shrimp, Fenneropenaeus chinensis following hypoxic exposure - Liu-Zhi Wei; Xiu-Mei Zhang; Jian Li; Guo-Qiang Huang (Aquaculture International, 2008)

Solid Substrate–Room Temperature Phosphorimetry for the Determination of Trace Terbutaline Sulfate Based on Its Inhibition Oxidation of Rhodamine 6G by Sodium Periodate - Jia-Ming Liu; Fei Gao; Wen-Yan Gao; Li-Qing Zeng; Xiao-Mei Huang; Zhi-Ming Li; Xiu-Chai Huang; Wei-Nv Lin; Fang-Mei Wang; Chang-Ling Nie (Journal of Fluorescence, 2008)

Highly efficient Agrobacterium-mediated transformation of embryogenic cell suspensions of Musa acuminata cv. Mas (AA) via a liquid co-cultivation system - Xia Huang; Xue-Lin Huang; Wang Xiao; Jie-Tang Zhao; Xue-Mei Dai; Yun-Feng Chen; Xiao-Ju Li (Plant Cell Reports, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Spatiotemporal expression of zebrafish D-amino acid oxidase during early embryogenesis - Yau-Hung Chen; Wei-Li Chen; Yun-Hsin Wang; Mei-Yun Huang; Ming-Kai Chern (Fish Physiology and Biochemistry, 2007)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

Synthesis of Site-Specifically Dimethylated and Trimethylated Peptides Derived from Histone H3 N-Terminal Tail - Zhi-Ping Huang; Jin-Tang Du; Yu-Fen Zhao; Yan-Mei Li (International Journal of Peptide Research and Therapeutics, 2006)

Studies on the Interaction of Tricyclazole with β-cyclodextrin and human Serum Albumin by Spectroscopy - Hua-Xin Zhang; Xing Huang; Ping Mei; Ke-Hua Li; Cheng-Nong Yan (Journal of Fluorescence, 2006)

Augmentation by citalopram of risperidone-induced monoamine release in rat prefrontal cortex - Mei Huang; Junji Ichiwaka; Zhu Li; Jin Dai; Herbert Y. Meltzer (Psychopharmacology, 2006)

ACP-103, a 5-HT2A/2C inverse agonist, potentiates haloperidol-induced dopamine release in rat medial prefrontal cortex and nucleus accumbens - Zhu Li; Junji Ichikawa; Mei Huang; Adam J. Prus; Jin Dai; Herbert Y. Meltzer (Psychopharmacology, 2005)

Fast screening target sites for RNA interference using a cell-free system - Huang Mei; Jia Fang-Jun; Li Chong-Yong; Li Yi-Ping; Guo Li-He (Biotechnology Letters, 2005)

Vertical Distribution of Soil Organic Carbon in China - Shaoqlang Wang; Mei Huang; Xuemei Shao; Robert A. Mickler; Kerang Li; Jingjun Ji (Environmental Management, 2004)

A G-Quadruplex Ligand 3,3′-Diethyloxadicarbocyanine Iodide Induces Mitochondrion-Mediated Apoptosis But Not Decrease of Telomerase Activity in Nasopharyngeal Carcinoma NPC-TW01 Cells - Chung-Pin Li; Jen-Hsin Huang; Ai-Chi Chang; Yi-Mei Hung; Chao-Hsiung Lin; Yee Chao; Shou-Dong Lee; Jacqueline Whang-Peng; Tze-Sing Huang (Pharmaceutical Research, 2004)

Minimizing phenol pollution in sugarcane stem apical meristem culture - Cheng-Mei Huang; Yang-Rui Li; Yan-Ping Ye (Sugar Tech, 2003)

Transport and Metabolic Characterization of Caco-2 Cells Expressing CYP3A4 and CYP3A4 Plus Oxidoreductase - Ming Hu; Yiqi Li; Christine M. Davitt; Shiew-Mei Huang; Kenneth Thummel; Bruce W. Penman; Charles L. Crespi (Pharmaceutical Research, 1999)